Image forming apparatus and image forming method

By using a cleaning blade made of polyurethane resin, its indentation elastic modulus and surface distribution characteristics of F and Si, the problems of toner film formation and cleaning blade wear in the prior art are solved, and more efficient images are achieved Form and clean the effect.

CN119439673APending Publication Date: 2025-02-14FUJIFILM BUSINESS INNOVATION CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410162238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-02-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the indentation elastic modulus of the cleaning blade is too high or the total amount of surfaces F and Si is insufficient, resulting in toner film formation on the surface of the transfer opposite conveyor belt, and the cleaning blade is seriously worn.

Method used

The cleaning scraper consisting of polyurethane resin is used, and the indentation elastic modulus at the surface in contact with the transfer opposite conveyor belt is 15MPa or more but not more than 35MPa, and the total F and Si in the area within 200nm from the contact surface is The amount accounts for more than 75% of the total amount of F and Si within 5 μm of the surface.

Benefits of technology

It effectively suppresses toner film formation on the surface of the transfer-opposed conveyor belt, reduces wear of the cleaning blade, and improves the cleaning performance and equipment life of the image forming device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119439673A_ABST
    Figure CN119439673A_ABST
Patent Text Reader

Abstract

The invention relates to an image forming apparatus and an image forming method. The image forming apparatus includes: an image holder; a charging member; a developing member accommodating an electrostatic latent image developer containing toner having toner particles; a transfer member; and a cleaning device that has a cleaning blade that is in contact with and cleans the outer peripheral surface of the transfer-facing conveyor belt, is made of a polyurethane resin, and has an indentation elastic modulus at the surface in contact with the transfer-facing conveyor belt of from 15 MPa to 35 MPa (inclusive), and an indentation elastic modulus at the surface in contact with the transfer-facing conveyor belt of from 15 MPa to 35 MPa (inclusive), and an indentation elastic modulus at the surface in contact with the transfer-facing conveyor belt of from 15 MPa to 35 MPa (inclusive). The total amount of F and Si present within 200 nm from the surface in contact with the transfer-facing conveyor belt accounts for 75% or more of the total amount of F and Si present within 5 [mu] m from the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an image forming device and an image forming method. Background Art

[0002] In an image forming apparatus (copier, fax machine, printer, etc.) using an electrophotographic method, a toner image formed on the surface of an image holder is transferred to the surface of a recording medium and fixed to the recording medium, thereby forming an image. In addition, when such a toner image is transferred to a recording medium, from the viewpoint of improving transferability, there is an image forming apparatus that is provided with a transfer counter conveyor belt that contacts the surface of the recording medium opposite to the surface to which the toner image is transferred. In addition, a cleaning blade is used to clean the outer peripheral surface of the transfer counter conveyor belt.

[0003] For example, Patent Document 1 discloses "a cleaning blade formed by cutting a plate-shaped body made of a cured polyurethane resin composition, wherein 4 atom % or more of silicon atoms (Si) are present on the end face of the cleaning blade formed by the cutting due to adhesion and oxidation treatment of organic siloxane."

[0004] Patent Document 1: Japanese Patent Application Publication No. 2001-051565 Summary of the invention

[0005] The object of the present invention is to provide an image forming apparatus and an image forming method in which the formation of colorant film on the surface of a transfer opposing conveyor belt is suppressed and the wear of the cleaning scraper is suppressed, compared with a cleaning scraper having an indentation elastic modulus of more than 35 MPa at the surface in contact with the transfer opposing conveyor belt or a cleaning scraper having a total amount of F and Si within 200 nm from the surface in contact with the transfer opposing conveyor belt that is less than 75% of the total amount of F and Si within 5 μm from the surface.

[0006] Means for solving the above-mentioned problems include the following.

[0007] <1> An image forming apparatus comprising:

[0008] Image holding body;

[0009] a charging member for charging the surface of the image holding member;

[0010] an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member;

[0011] A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent of the entire toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer;

[0012] a transfer member having a transfer counter-conveyor belt in contact with a surface of a recording medium opposite to a surface on which the toner image is transferred, and transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; and

[0013] A cleaning device having a cleaning scraper, the cleaning scraper contacts with and cleans the outer peripheral surface of the transfer counter conveyor belt, and is made of a polyurethane resin, the indentation elastic modulus at the surface in contact with the transfer counter conveyor belt is greater than 15 MPa and less than 35 MPa, and the total amount of F and Si existing within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si existing within 5 μm from the surface.

[0014] <2> The image forming apparatus according to <1>, wherein:

[0015] The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.

[0016] <3> The image forming apparatus according to <1> or <2>, wherein:

[0017] The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.

[0018] <4> The image forming apparatus according to any one of <1> to <3>, wherein:

[0019] The indentation elastic modulus of the cleaning blade is 20 MPa or more and 30 MPa or less.

[0020] <5> The image forming apparatus according to any one of <1> to <4>, wherein:

[0021] In the cleaning blade, the total amount of F and Si present within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.

[0022] <6> The image forming apparatus according to any one of <1> to <5>, wherein

[0023] In the cleaning blade, a total amount of F and Si present on a surface in contact with the transfer opposing conveyor belt is 15 atm % or more.

[0024] <7> The image forming apparatus according to <6>, wherein:

[0025] In the cleaning blade, a total amount of F and Si present on a surface in contact with the transfer opposing conveyor belt is 18 atm % or more and 25 atm % or less.

[0026] <8> The image forming apparatus according to any one of <1> to <7>, wherein:

[0027] In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface in contact with the transfer opposing conveyor belt is 0.3 atm % or more.

[0028] <9> The image forming apparatus according to <8>, wherein:

[0029] In the cleaning blade, a total amount of F and Si present at a position 50 nm from a surface in contact with the transfer opposing conveyor belt is 0.3 atm % or more and 2.0 atm % or less.

[0030] <10> The image forming apparatus according to any one of <1> to <9>, wherein:

[0031] The cleaning blade contains a silicone polymer in a surface layer that contacts the transfer opposing conveyor belt.

[0032] <11> The image forming apparatus according to any one of <1> to <10>, wherein

[0033] The cleaning blade contacts the transfer counter conveyor belt with a pressing force of 1.5 gf / mm or more and 3.5 gf / mm or less.

[0034] <12> The image forming apparatus according to any one of <1> to <11>, wherein

[0035] The transfer counter conveyor belt includes a conductive elastic layer containing carbon black and a surface layer containing 35 mass % or more of polytetrafluoroethylene particles.

[0036] <13> An image forming method, comprising:

[0037] A charging process to charge the surface of the image holding body;

[0038] An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member;

[0039] A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less;

[0040] a transfer step of bringing a transfer counter conveyor belt into contact with a surface of a recording medium opposite to a surface on which the toner image is transferred, so as to transfer the toner image formed on the surface of the image holder to the surface of the recording medium; and

[0041] A cleaning process, wherein a cleaning scraper is brought into contact with the outer peripheral surface of the transfer counter conveyor belt and cleans it, wherein the cleaning scraper is made of polyurethane resin, and the indentation elastic modulus at the surface in contact with the transfer counter conveyor belt is greater than 15 MPa and less than 35 MPa, and the total amount of F and Si within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si within 5 μm from the surface.

[0042] Effects of the Invention

[0043] According to the invention involved in <1>, there is provided an image forming apparatus in which toner filming on the surface of a transfer opposing conveyor belt is suppressed and wear of a cleaning scraper is suppressed, compared to an image forming apparatus having a cleaning scraper having an indentation elastic modulus of more than 35 MPa at the surface in contact with the transfer opposing conveyor belt or a cleaning scraper having a total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing conveyor belt that is less than 75% of the total amount of F and Si present within 5 μm from the surface.

[0044] According to the invention of <2>, an image forming apparatus having excellent low-temperature fixing property of an image is provided, compared with an image forming apparatus in which the releasing agent existing in the region within 800 nm from the surface of the toner particle accounts for less than 75% of the releasing agent in the entire toner particle.

[0045] According to the invention involved in <3>, an image forming apparatus is provided that has excellent low-temperature fixing property of an image compared to an image forming apparatus in which the melting temperature of a release agent exceeds 75°C, and an image forming apparatus is provided that suppresses the formation of colorant film on the surface of a transfer opposing conveyor belt compared to an image forming apparatus in which the melting temperature of a release agent is lower than 70°C.

[0046] According to the invention involved in <4>, an image forming device is provided in which the indentation elastic modulus of the cleaning scraper is less than 20MPa, and the image forming device is suppressed from leaking the colorant at the contact position between the transfer opposing conveyor belt and the cleaning scraper; and an image forming device is provided in which the indentation elastic modulus of the cleaning scraper exceeds 30MPa, and the image forming device is suppressed from forming the colorant film on the surface of the transfer opposing conveyor belt.

[0047] According to the invention involved in <5>, there is provided an image forming apparatus in which wear at the contact portion of the cleaning blade is suppressed compared to an image forming apparatus having a cleaning blade in which the total amount of F and Si existing within 200 nm from the surface in contact with the transfer opposing conveyor belt is less than 85% of the total amount of F and Si existing within 5 μm from the surface.

[0048] According to the invention of <6> or <7>, there is provided an image forming apparatus having a cleaning blade having a surface in contact with a transfer counter conveyor belt in which the total amount of F and Si is less than 15 atm %, and in which wear of the contact portion of the cleaning blade is suppressed.

[0049] According to the invention described in <8> or <9>, there is provided an image forming apparatus in which the wear over time of the contact portion of the cleaning blade is suppressed compared to an image forming apparatus having a cleaning blade in which the total amount of F and Si present at a position 50 nm from the surface in contact with the transfer opposing conveyor belt is less than 0.3 atm %.

[0050] According to the invention <10>, there is provided an image forming apparatus in which abrasion of the contact portion of the cleaning blade is suppressed compared to an image forming apparatus including a cleaning blade whose surface layer in contact with the transfer opposing conveyor belt does not contain a silicone polymer but contains a fluorine compound.

[0051] According to the invention involved in <11>, there is provided an image forming device in which a cleaning scraper contacts a transfer counter conveyor belt with a pressing force less than 1.5 gf / mm, thereby suppressing the occurrence of toner leakage at the contact position between the transfer counter conveyor belt and the cleaning scraper; and there is provided an image forming device in which a cleaning scraper contacts a transfer counter conveyor belt with a pressing force greater than 3.5 gf / mm, thereby further suppressing the occurrence of toner filming on the surface of the transfer counter conveyor belt.

[0052] According to the invention <12>, there is provided an image forming apparatus which suppresses toner leakage at the contact position between the transfer counter conveyor belt and the cleaning blade compared to an image forming apparatus having a conductive elastic layer containing no carbon black.

[0053] According to the invention involved in <13>, there is provided an image forming method in which colorant filming on the surface of a transfer opposing conveyor belt is suppressed and wear of a cleaning scraper is suppressed, compared to an image forming method including a cleaning process using a cleaning scraper having an indentation elastic modulus exceeding 35 MPa at the surface in contact with the transfer opposing conveyor belt or a cleaning scraper in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing conveyor belt is less than 75% of the total amount of F and Si present within 5 μm from the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Embodiments of the present invention will be described in detail with reference to the following drawings.

[0055] Figure 1 1 is a schematic structural diagram showing an example of a transfer counter conveyor belt used in the present embodiment;

[0056] Figure 2 is a schematic structural diagram showing an example of an image forming apparatus according to the present embodiment;

[0057] Figure 3 This is a schematic diagram for explaining the pressing force of the cleaning blade on the transfer counter conveyor belt. DETAILED DESCRIPTION

[0058] Hereinafter, the present embodiment as an example of the present invention will be described. These descriptions and examples are for illustrating the embodiment and do not limit the scope of the embodiment.

[0059] In the numerical ranges recorded in stages in this embodiment, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in this embodiment, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0060] In the present embodiment, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0061] While the embodiment is described with reference to the drawings in this embodiment, the structure of the embodiment is not limited to the structure shown in the drawings. In addition, the sizes of the components in each figure are conceptual, and the relative relationship between the sizes of the components is not limited to this.

[0062] In this embodiment, each component may include a plurality of corresponding substances. In this embodiment, when the amount of each component in the composition is mentioned, if there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition.

[0063] [Image forming apparatus]

[0064] The image forming device involved in this embodiment comprises: an image holder; a charging member for charging the surface of the image holder; an electrostatic latent image forming member for forming an electrostatic latent image on the surface of the charged image holder; a developing member for accommodating an electrostatic latent image developer containing a colorant having colorant particles, and developing the electrostatic latent image formed on the surface of the image holder into a colorant image by the electrostatic latent image developer; a transfer member having a transfer opposing conveyor belt in contact with the side of the recording medium opposite to the side on which the colorant image is transferred (hereinafter referred to as the "back side"), and transferring the colorant image formed on the surface of the image holder to the surface of the recording medium; and a cleaning device having a cleaning scraper, wherein the cleaning scraper is in contact with the outer peripheral surface of the transfer opposing conveyor belt and cleans it.

[0065] In the toner particles, the releasing agent present in a region within 800 nm from the surface accounts for 70% or more of the releasing agent in the entire toner particles, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less.

[0066] The cleaning blade is made of polyurethane resin, and the indentation elastic modulus of the surface in contact with the transfer counter conveyor belt is 15 MPa or more and 35 MPa or less. Furthermore, the total amount of F and Si present within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.

[0067] With the above-described configuration, the image forming apparatus according to the present embodiment suppresses toner filming on the transfer opposing conveyor belt surface and suppresses abrasion of the cleaning blade. The reason for this is presumably as follows.

[0068] In the image forming apparatus, vibration often occurs at the transfer section of the toner image to the recording medium due to the influence of the passage of the recording medium, etc. In the case of a cleaning device that further cleans the transfer member having the transfer opposing conveyor belt by bringing a cleaning blade into contact with the outer peripheral surface of the transfer opposing conveyor belt that contacts the back side of the recording medium, the load applied to the cleaning blade increases instantaneously due to the influence of the vibration, causing the pressing of the cleaning blade against the transfer opposing conveyor belt to become unstable, and sometimes the cleaning performance becomes unstable.

[0069] Therefore, in order to improve the durability against vibration (i.e., the property of being less susceptible to the influence of external factors such as vibration) in the cleaning device of the transfer counter conveyor belt, a method of providing a load adjustment mechanism on the cleaning blade may be considered. That is, the following method may be considered: by controlling the load applied from the cleaning blade to the transfer counter conveyor belt using the load adjustment mechanism, the cleaning blade is continuously pressed with a stable pressure, thereby stabilizing the cleaning performance.

[0070] However, the control mechanism in the image forming apparatus becomes complicated by providing a load adjustment mechanism, which becomes a factor of cost increase. Therefore, a method of achieving stable cleaning performance for the transfer counter conveyor belt even without providing a load adjustment mechanism is required.

[0071] Furthermore, from the viewpoint of suppressing energy consumption, a toner image with excellent low-temperature fixing properties is desired. Therefore, from the viewpoint of improving the low-temperature fixing properties of the image, a method of using a toner having toner particles in which a low melting temperature wax is concentrated in the surface layer (specifically, a toner in which the release agent present in the region within 800 nm from the surface of the toner particle is more than 70% of the release agent of the entire toner particle, and the melting temperature of the release agent is more than 65°C and less than 80°C) has been studied. However, when using toner particles in which a low melting temperature wax is concentrated in the surface layer, toner filming sometimes occurs easily on the surface of the transfer opposing conveyor belt. This is believed to be because the surface of the toner particles in which the low melting temperature wax is concentrated in the surface layer as described above is easily softened, and thus easily crushed by the pressure from the cleaning scraper.

[0072] From the above viewpoints, in an image forming apparatus that uses colorant particles that have a low melting temperature wax concentrated in the surface layer as described above and has a cleaning device that uses a cleaning scraper to clean the surface of a transfer counter conveyor belt, it is required to suppress the formation of colorant film on the surface of the transfer counter conveyor belt even if a load adjustment mechanism is not provided for the cleaning device.

[0073] In addition, a method of increasing the pressure of the cleaning blade pressed against the transfer belt to improve the scraping property and thus suppress the toner filming can be considered. However, if the pressure is increased, the wear of the cleaning blade will become serious and the life of the cleaning blade will be shortened. Therefore, in addition to suppressing the toner filming, it is also required to suppress the wear of the cleaning blade.

[0074] In contrast, in the image forming apparatus according to the present embodiment, a cleaning blade is used in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface. That is, in the cleaning blade, F and Si are concentrated near the contact portion with the transfer counter conveyor belt. The friction of the cleaning blade is reduced by the presence of at least one of F and Si at the contact portion, thereby suppressing the wear of the cleaning blade. Furthermore, even in the case where the load applied to the cleaning blade increases momentarily due to vibration, the behavior at the front end of the contact portion is stable due to the reduction of the friction of the cleaning blade. As a result, stable cleaning performance can be achieved.

[0075] In addition, in this embodiment, a cleaning blade having an indentation elastic modulus of 35 MPa or less at the surface in contact with the transfer counter conveyor belt is used, that is, the surface pressure applied from the cleaning blade to the transfer counter conveyor belt is reduced. Therefore, even if toner particles that have a low melting temperature wax concentrated in the surface layer as described above are used, toner filming on the surface of the transfer counter conveyor belt can be suppressed.

[0076] In summary, it is presumed that according to the image forming apparatus according to the present embodiment, toner filming on the transfer opposing conveyor belt surface can be suppressed, and wear of the cleaning blade can be suppressed.

[0077] (Toner)

[0078] The toner contained in the electrostatic latent image developer used in the image forming apparatus according to the present embodiment is described. The toner contains toner particles, in which the release agent present in the region within 800 nm from the surface of the toner particles accounts for more than 70% of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. to 80° C.

[0079] The toner particles contain a release agent and may further contain a binder resin. Furthermore, the toner particles may further contain other internal additives such as a colorant.

[0080] -Release agent-

[0081] The melting temperature of the release agent is 65° C. to 80° C., for example, preferably 68° C. to 77° C., more preferably 70° C. to 75° C. When the melting temperature of the release agent is 80° C. or less, the low-temperature fixability of the image can be improved. On the other hand, when the melting temperature of the release agent is 65° C. or more, toner filming on the transfer belt surface can be suppressed.

[0082] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) according to the “melting peak temperature” described in the method for determining the melting temperature in JIS K-7121-1987 “Methods for determining transition temperatures of plastics”.

[0083] Regarding the release agent, 70% or more of all the release agent exists within 800 nm from the surface of the toner particles (hereinafter, the proportion of the release agent existing within 800 nm from the surface of the toner particles is also referred to as "surface layer proportion of the release agent").

[0084] The surface ratio of the release agent is 70% or more, for example, preferably 75% or more, more preferably 80% or more. The upper limit of the surface ratio of the release agent is preferably 100%. When the surface ratio of the release agent is 70% or more, the low temperature fixability of the image can be improved.

[0085] Here, the method for measuring the surface layer ratio of the release agent is described.

[0086] The measurement samples and images were prepared by the following method.

[0087] The toner is mixed with the epoxy resin and embedded in the epoxy resin to cure the epoxy resin. The cured product is cut using an ultrathin sectioning device (Ultracut UCT manufactured by Leica Corporation) to form a thin sheet sample with a thickness of more than 80 nm and less than 130 nm. Then, an ultra-high resolution field emission scanning electron microscope (FE-SEM. S-4800 manufactured by Hitachi High-Technologies Corporation) is used to obtain an SEM image of the thin sheet sample. In the SEM image, a cross section of a toner particle having a maximum length of more than 85% of the volume average particle size of the toner particle is selected, and the domain of the release agent is observed to determine the area of ​​the release agent of the entire toner particle and the area of ​​the release agent present in the region within 800 nm from the surface of the toner particle, and calculate the area ratio of the two (the area of ​​the release agent present in the region within 800 nm from the surface of the toner particle / the area of ​​the release agent of the entire toner particle). Then, the calculation is performed on 100 toner particles, and the average value is used as the surface ratio of the release agent.

[0088] The reason for selecting a colorant particle cross section whose maximum length is greater than 85% of the volume average particle size of the colorant particle is that a cross section less than 85% of the volume average particle size is predicted to be a cross section at the end of the colorant particle, and the state of the domain in the colorant particle will not be well reflected in the cross section at the end of the colorant particle.

[0089] As a control method for making the surface layer ratio of the release agent 70% or more, for example, there is a method of making the toner particles have a core-shell structure and using a release agent when forming the shell.

[0090] Examples of the release agent include hydrocarbon waxes such as paraffin wax, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0091] As a release agent, for example, hydrocarbon wax is preferably used. Hydrocarbon wax is a wax having a hydrocarbon as a skeleton, and examples thereof include Fischer-Tropsch wax, polyethylene wax (wax having a polyethylene skeleton), polypropylene wax (wax having a polypropylene skeleton), paraffin wax (wax having a paraffin skeleton), microcrystalline wax, etc. Among them, as a hydrocarbon wax, from the viewpoint of fixability, for example, Fischer-Tropsch wax, polyethylene wax or polypropylene wax is preferred. And, for example, from the viewpoint of fixability, it is preferred that the toner particles contain a plurality of hydrocarbon waxes.

[0092] The ratio of the hydrocarbon wax to the total release agent is, for example, preferably 85 mass % or more, preferably 95 mass % or more, and more preferably 100 mass %.

[0093] The content of the release agent is, for example, preferably 1% by mass to 20% by mass, more preferably 3% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and even more preferably 5% by mass to 15% by mass, relative to the entire toner particles.

[0094] -Bonding resin-

[0095] As the binder resin, for example, a polyester resin is preferably used. The ratio of the polyester resin to the total binder resin is, for example, preferably 75% by mass or more, preferably 90% by mass or more, and more preferably 100% by mass.

[0096] As the polyester resin, for example, a known amorphous polyester resin can be cited. The polyester resin can use a crystalline polyester resin together with the amorphous polyester resin. However, the crystalline polyester resin is preferably used in a range of 2% by mass or more and 40% by mass or less (for example, more preferably 2% by mass or more and 20% by mass or less) relative to the entire binder resin.

[0097] The "crystallinity" of a resin refers to having a clear endothermic peak in differential scanning calorimetry (DSC) rather than a step-like change in endothermic value. Specifically, it means that the half width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).

[0098] On the other hand, the "amorphous" nature of a resin means that the half width exceeds 10°C, the endothermic value shows a step-like change, or a clear endothermic peak cannot be confirmed.

[0099] Amorphous polyester resin

[0100] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, commercially available products or synthetic resins may be used as the non-crystalline polyester resin.

[0101] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.

[0102] The polycarboxylic acid may be used together with the dicarboxylic acid and a trivalent or higher carboxylic acid having a crosslinked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof.

[0103] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0104] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among them, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.

[0105] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerol, trimethylolpropane, and pentaerythritol.

[0106] The polyols may be used alone or in combination of two or more.

[0107] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 80° C. or lower, and more preferably 50° C. or higher and 65° C. or lower.

[0108] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for determining the glass transition temperature in JIS K 7121-1987 "Determination of Transition Temperature of Plastics".

[0109] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.

[0110] The number average molecular weight (Mn) of the amorphous polyester resin is preferably, for example, 2,000 or more and 100,000 or less.

[0111] The molecular weight distribution Mw / Mn of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0112] The weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement by GPC, GPC HLC-8120GPC manufactured by TOSOH CORPORATION is used as a measuring device, a TOSOH CORPORATION column TSKgel SuperHM-M (15 cm) is used, and THF solvent is used. The weight average molecular weight and the number average molecular weight are calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.

[0113] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water and alcohol generated during condensation.

[0114] In addition, when the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent can be added as a cosolvent to dissolve it. In this case, the polycondensation reaction is carried out while the cosolvent is removed by distillation. In the case of the presence of a monomer with poor compatibility in the copolymerization reaction, for example, the monomer with poor compatibility can be condensed in advance with an acid or alcohol to be polycondensed with the monomer, and then polycondensed together with the main component.

[0115] Crystalline polyester resin

[0116] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, as the crystalline polyester resin, a commercially available product may be used, and a synthetic resin may also be used.

[0117] Here, since the crystalline polyester resin easily forms a crystal structure, for example, it is preferable to use a polycondensate of a polymerizable monomer having a linear aliphatic group rather than a polycondensate of a polymerizable monomer having an aromatic group.

[0118] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.

[0119] The polycarboxylic acid may be used together with the dicarboxylic acid, and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 or more and 5 or less) alkyl esters.

[0120] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond can be used together with these dicarboxylic acids.

[0121] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0122] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-docosanediol. Among them, examples of the aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0123] As the polyol, a trivalent or higher alcohol having a cross-linked structure or a branched structure may be used together with the diol. Examples of the trivalent or higher alcohol include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0124] The polyols may be used alone or in combination of two or more.

[0125] Among these, for example, the content of the aliphatic diol in the polyol is preferably 80 mol % or more, and more preferably 90 mol % or more.

[0126] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.

[0127] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121-1987 "Determination of Transition Temperatures of Plastics".

[0128] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.

[0129] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a well-known production method.

[0130] Here, the binder resin may be used together with the polyester resin and other binder resins. As other binder resins, for example, styrene (meth) acrylic resins are preferably used.

[0131] -Styrene (meth) acrylic resin-

[0132] Styrene (meth) acrylic resin is a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth) acryloyl group. "(Meth) acrylic" includes both "acrylic" and "methacrylic". Furthermore, "(meth) acryloyl" includes both "acryloyl" and "methacryloyl".

[0133] Examples of monomers having a styrene skeleton (hereinafter referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more.

[0134] Among them, as the styrene-based monomer, for example, styrene is preferred from the viewpoint of reactivity, controllability of reaction, and availability.

[0135] Examples of monomers having a (meth)acryloyl group (hereinafter referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, and n-octadecyl (meth)acrylate). (meth)acrylate, such as pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, (meth)acrylamide, etc. The (meth)acrylic monomer may be used alone or in combination of two or more.

[0136] The copolymerization ratio of the styrene-based monomer and the (meth)acrylic-based monomer (based on mass, styrene-based monomer / (meth)acrylic-based monomer) is preferably, for example, 85 / 15 to 70 / 30.

[0137] From the viewpoint of suppressing the print-through of the image, the styrene (meth) acrylic resin preferably has a cross-linked structure. Examples of the styrene (meth) acrylic resin having a cross-linked structure include a cross-linked product obtained by copolymerizing and cross-linking at least a monomer having a styrene skeleton, a monomer having a (meth) acrylic skeleton, and a cross-linking monomer.

[0138] Examples of the crosslinkable monomer include bifunctional or higher-functional crosslinking agents.

[0139] Examples of the bifunctional crosslinking agent include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylenebis(meth)acrylamide, decanediol diacrylate, glycidyl(meth)acrylate, etc.), polyester di(meth)acrylate, and 2-([1'-methylpropyleneamino]carboxyamino)ethyl methacrylate.

[0140] Examples of the polyfunctional crosslinking agent include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., tetramethylolmethane tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, diallyl chlorendonate, etc.

[0141] The copolymerization ratio of the crosslinkable monomer to all monomers (based on mass, crosslinkable monomer / all monomers) is preferably, for example, 2 / 1000 to 30 / 1000.

[0142] From the viewpoint of suppressing the strike-through of an image, the weight average molecular weight of the styrene (meth) acrylic resin is, for example, preferably 30,000 to 200,000, preferably 40,000 to 100,000, and more preferably 50,000 to 80,000.

[0143] The weight average molecular weight of the styrene (meth) acrylic resin is a value measured by the same method as the weight average molecular weight of the polyester resin.

[0144] From the viewpoint of balancing the fluidity and storage properties of the colorant and suppressing the print-through of the image, the content of the styrene (meth) acrylic resin is preferably, for example, 10% by mass or more and 30% by mass or less, preferably 12% by mass or more and 28% by mass or less, and more preferably 15% by mass or more and 25% by mass or less, relative to the colorant particles.

[0145] Furthermore, other binding resins may be used simultaneously as the binding resin.

[0146] As other binder resins, for example, there can be mentioned vinyl resins composed of homopolymers of monomers such as styrenes (for example, styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (for example, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (for example, acrylonitrile, methacrylonitrile, etc.), vinyl ethers (for example, vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (for example, vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (for example, ethylene, propylene, butadiene, etc.), or copolymers formed by combining two or more of these monomers.

[0147] Other examples of binder resins include epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosins and other non-vinyl resins, mixtures thereof with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers under the coexistence of the above-mentioned resins.

[0148] These other binder resins may be used alone or in combination of two or more.

[0149] The content of the binder resin is, for example, preferably 40 mass % to 95 mass % inclusive, more preferably 50 mass % to 90 mass % inclusive, and further preferably 60 mass % to 85 mass % inclusive, based on the entire toner particles.

[0150] -Colorants-

[0151] Examples of the colorant include various pigments such as carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose Bengal, aniline blue, ultramarine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based.

[0152] The coloring agent may be used alone or in combination of two or more.

[0153] The colorant may be a surface-treated colorant as required, or may be used together with a dispersant. Furthermore, a plurality of colorants may be used simultaneously.

[0154] The content of the colorant is, for example, preferably 1 mass % to 30 mass % inclusive, and more preferably 3 mass % to 15 mass % inclusive, based on the entire toner particles.

[0155] -Other additives-

[0156] Examples of other additives in the toner include well-known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.

[0157] -Characteristics of toner particles-

[0158] The toner particles may be toner particles of a single-layer structure, or toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) coating the core, and preferably a core-shell structure. The toner particles of a core-shell structure preferably consist of a core composed of a binder resin and a colorant, and a coating layer composed of a binder resin and a release agent.

[0159] The volume average particle size (D50v) of the toner particles is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.

[0160] Various average particle diameters and various particle size distribution indices of the toner particles were measured using Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte solution was measured using ISOTON-II (manufactured by Beckman Coulter, Inc.).

[0161] During measurement, 0.5 mg to 50 mg of a measurement sample is added as a dispersant to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate), and this is added to 100 ml to 150 ml of an electrolyte.

[0162] The electrolyte in which the sample was suspended was dispersed by an ultrasonic disperser for 1 minute, and the particle size distribution of particles with a particle size ranging from 2 μm to 60 μm was measured by Coulter Multisizer II using an aperture of 100 μm. The number of particles to be sampled was 50,000.

[0163] The cumulative distribution of volume and number is plotted for the particle size range (channel) divided based on the measured particle size distribution from the small diameter side, and the particle size when the cumulative amount reaches 16% is defined as the volume particle size D16v and the number average particle size D16p, the particle size when the cumulative amount reaches 50% is defined as the volume average particle size D50v and the number average particle size D50p, and the particle size when the cumulative amount reaches 84% ​​is defined as the volume particle size D84v and the number average particle size D84p.

[0164] Use them, by (D84v / D16v) 1 / 2 Calculate the volume average particle size distribution index (GSDv) from (D84p / D16p) 1 / 2 Calculate the number average particle size distribution index (GSDp).

[0165] The shape factor SF1 of the toner particles is, for example, preferably 110 or more and 150 or less, and more preferably 120 or more and 140 or less.

[0166] The shape factor SF1 is obtained by the following formula.

[0167] Formula: SF1 = (ML 2 / A)×(π / 4)×100

[0168] In the above formula, ML represents the absolute maximum length of the toner, and A represents the projected area of ​​the toner.

[0169] Specifically, the shape factor SF1 is digitized mainly by analyzing a microscope image or a scanning electron microscope image using an image analyzer, and is calculated as follows: That is, an optical microscope image of particles scattered on the surface of a slide is introduced into a Luzex image analyzer using a camera, the maximum length and projected area of ​​100 particles are obtained, and the calculation is performed using the above formula to obtain the average value.

[0170] -External Additives-

[0171] The toner may contain an external additive in addition to the toner particles.

[0172] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0173] The surface of the inorganic particles as an external additive is preferably subjected to a hydrophobic treatment, for example. The hydrophobic treatment is carried out, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.

[0174] The amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.

[0175] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate (PMMA), melamine resin, and the like), cleaning aids (for example, metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight bodies).

[0176] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.

[0177] -Method for producing toner-

[0178] The toner used in the image forming apparatus according to the present embodiment is produced by producing toner particles and, if the toner particles further contain an external additive, adding the external additive to the toner particles.

[0179] The toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) and wet methods (e.g., aggregation method, suspension polymerization method, dissolution suspension method, etc.). These methods are not particularly limited, and well-known methods can be used. Among them, it is preferred to obtain the toner particles by, for example, the aggregation method.

[0180] The following is a description of the details of each step of the aggregation method. In the following description, a method for obtaining toner particles containing a colorant is described, but a colorant can be used as needed. Of course, other additives besides the colorant can also be used.

[0181] ·Resin particle dispersion preparation process

[0182] First, a resin particle dispersion in which polyester resin particles serving as a binder resin are dispersed, a colorant dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0183] The polyester resin particle dispersion is prepared by, for example, dispersing the polyester resin particles in a dispersion medium using a surfactant.

[0184] Examples of the dispersion medium used for the polyester resin particle dispersion include aqueous media.

[0185] Examples of the aqueous medium include water such as distilled water and deionized water; and alcohols, etc. These may be used alone or in combination of two or more.

[0186] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Among them, anionic surfactants and cationic surfactants are particularly useful. Nonionic surfactants may be used together with anionic surfactants or cationic surfactants.

[0187] The surfactant may be used alone or in combination of two or more.

[0188] As a method for dispersing polyester resin particles in a dispersion medium, for example, a conventional dispersion method using a rotary shearing homogenizer or a ball mill, a sand mill, a DYNO-MILL, etc. having a medium can be cited. In addition, the polyester resin particles can also be dispersed in a dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method refers to a method in which a resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to an organic continuous phase (O phase) for neutralization, and then water (W phase) is added to perform a phase inversion from W / O to O / W, thereby dispersing the resin in a particle form in an aqueous medium.

[0189] The volume average particle size of the polyester resin particles dispersed in the polyester resin particle dispersion is, for example, preferably 0.01 μm to 1 μm, more preferably 0.08 μm to 0.8 μm, and further preferably 0.1 μm to 0.6 μm.

[0190] Regarding the volume average particle size of the polyester resin particles, the particle size distribution obtained by the measurement by a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by HORIBA, Ltd.) is used to draw the cumulative distribution of the volume for the particle size range (channel) divided from the small particle size side, and the particle size when the accumulation reaches 50% relative to all particles is taken as the volume average particle size D50v. In addition, the volume average particle size of particles in other dispersions is also measured in the same manner.

[0191] The content of the polyester resin particles contained in the polyester resin particle dispersion is, for example, preferably 5 mass % or more and 50 mass % or less, and more preferably 10 mass % or more and 40 mass % or less.

[0192] Similar to the polyester resin particle dispersion, a colorant dispersion and a release agent particle dispersion are also prepared. That is, the dispersion medium, dispersion method, volume average particle size of the particles, and particle content in the polyester resin particle dispersion are also the same in the colorant dispersion and the release agent particle dispersion.

[0193] ·First agglomerated particle forming step

[0194] Next, the polyester resin particle dispersion and the colorant dispersion are mixed.

[0195] Then, the polyester resin particles and the colorant particles are heterogeneously aggregated in the mixed dispersion to form target first aggregated particles having a diameter close to that of toner particles and containing the polyester resin particles and the colorant particles.

[0196] Furthermore, the first aggregated particles may contain the release agent particles by mixing the release agent particle dispersion as necessary.

[0197] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, pH 2 or more and pH 5 or less), and after a dispersion stabilizer is added as needed, it is heated to a temperature close to the glass transition temperature of the polyester resin (specifically, for example, -30°C or more and -10°C or less of the glass transition temperature of the polyester resin) to aggregate the particles dispersed in the mixed dispersion to form first aggregated particles.

[0198] In the first agglomerated particle formation step, for example, the mixed dispersion can be stirred using a rotary shearing homogenizer, a coagulant can be added at room temperature (e.g., 25° C.), the pH of the mixed dispersion can be adjusted to acidic (e.g., pH 2 or more and pH 5 or less), a dispersion stabilizer can be added as needed, and then heating can be performed.

[0199] Examples of the coagulant include surfactants having polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of the coagulant used can be reduced, thereby improving the charging characteristics.

[0200] An additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As such an additive, a chelating agent may be used.

[0201] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0202] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0203] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.

[0204] · Second aggregated particle forming step

[0205] After obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the first aggregated particle dispersion, the polyester resin particle dispersion, and the release agent particle dispersion are further mixed. The polyester resin particle dispersion and the release agent particle dispersion may be mixed in advance and then the mixed solution may be mixed into the first aggregated particle dispersion.

[0206] Then, in the mixed dispersion in which the first aggregated particles, the polyester resin particles, and the release agent particles are dispersed, the polyester resin particles and the release agent particles are aggregated so that the polyester resin particles and the release agent particles adhere to the surfaces of the first aggregated particles, thereby forming second aggregated particles.

[0207] Specifically, for example, in the first aggregated particle forming step, when the first aggregated particles reach the target particle size, a dispersion in which polyester resin particles and release agent particles are dispersed is mixed with the first aggregated particle dispersion. Next, the mixed dispersion is heated at a temperature below the glass transition temperature of the polyester resin, the pH of the mixed dispersion is adjusted to, for example, a range of about 6.5 to 8.5, and aggregation is stopped.

[0208] Thus, second aggregated particles are obtained in which the polyester resin particles and the release agent particles are aggregated so as to adhere to the surfaces of the first aggregated particles.

[0209] Melting / combination process

[0210] Next, the second aggregated particle dispersion containing the second aggregated particles is heated, for example, to a temperature above the glass transition temperature of the polyester resin (for example, a temperature 10°C to 50°C higher than the glass transition temperature of the polyester resin) to melt / combine the second aggregated particles to form toner particles.

[0211] Through the above steps, toner particles are obtained.

[0212] In addition, the colorant particles can also be manufactured through the following steps: after obtaining the second agglomerated particle dispersion in which the second agglomerated particles are dispersed, further mixing the second agglomerated particle dispersion and the polyester resin particle dispersion in which the polyester resin particles are dispersed to agglomerate the polyester resin particles so as to further adhere to the surface of the second agglomerated particles to form third agglomerated particles; and heating the third agglomerated particle dispersion in which the third agglomerated particles are dispersed to melt / combine the third agglomerated particles to form colorant particles.

[0213] After the melting / combining step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles.

[0214] The washing process is not particularly limited, but from the viewpoint of chargeability, it is preferred to fully perform replacement washing with deionized water. In addition, the solid-liquid separation process is not particularly limited, but from the viewpoint of productivity, it is preferred to perform suction filtration, pressure filtration, etc. In addition, the method of the drying process is not particularly limited, but from the viewpoint of productivity, it is preferred to perform freeze drying, airflow drying, fluidized drying, vibration-type fluidized drying, etc.

[0215] The toner according to the present embodiment is produced by, for example, adding an external additive to dry toner particles and mixing them. The mixing is preferably performed by, for example, a V mixer, a Henschel mixer, a Lödige mixer, etc. Furthermore, coarse particles of the toner may be removed by using a vibration sieving machine, a wind sieving machine, etc. as needed.

[0216] - Electrostatic latent image developer -

[0217] In this embodiment, the electrostatic latent image developer contained in the developing member contains at least the above-mentioned toner. The electrostatic latent image developer may be a single-component developer containing only the toner, or a two-component developer in which the toner and a carrier are mixed.

[0218] The carrier is not particularly limited, and known carriers can be cited. Examples of the carrier include a coated carrier in which the surface of a core material containing magnetic powder is coated with a resin; a magnetic powder dispersed carrier prepared by dispersing magnetic powder in a matrix resin; and a resin impregnated carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersed carrier and the resin impregnated carrier can be a carrier in which the constituent particles of the carrier are used as a core material and the surface is coated with a resin.

[0219] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; and magnetic oxides such as ferrite and magnetite.

[0220] Examples of the conductive particles include particles of metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0221] Examples of the coating resin and the matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, linear silicone resin containing an organic siloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The coating resin and the matrix resin may contain additives such as a conductive material.

[0222] The method of coating the surface of the core material with a resin includes a method of coating with a coating layer forming solution obtained by dissolving a coating resin and various additives (used as needed) in an appropriate solvent. The solvent is not particularly limited, and can be selected by considering the type of resin used and coating suitability. Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution; a spraying method in which the coating layer forming solution is sprayed on the surface of the core material; a fluidized bed method in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and then the solvent is removed.

[0223] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is, for example, preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0224] (Cleaning scraper)

[0225] A cleaning blade used in the image forming apparatus according to the present embodiment is described. The cleaning blade is made of polyurethane resin. The indentation elastic modulus at the surface (contact portion) of the cleaning blade that contacts the transfer counter conveyor belt is 15 MPa or more and 35 MPa or less. Furthermore, the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade that contacts the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.

[0226] The cleaning blade may be a single-layer blade having a single layer, a double-layer blade having an edge layer (a layer in contact with the transfer counter-conveyor belt) and a back layer, or a structure having three or more layers stacked.

[0227] -Indentation elastic modulus-

[0228] The indentation elastic modulus at the surface (contact portion) of the cleaning scraper in contact with the transfer opposing conveyor belt is 15 MPa or more and 35 MPa or less. By having an indentation elastic modulus of 15 MPa or more, it is possible to suppress the toner from being scraped off at the contact position between the transfer opposing conveyor belt and the cleaning scraper. By having an indentation elastic modulus of 35 MPa or less, it is possible to suppress the toner from being filmed on the surface of the transfer opposing conveyor belt. Furthermore, the indentation elastic modulus is preferably, for example, 20 MPa or more and 30 MPa or less, and more preferably 22 MPa or more and 28 MPa or less.

[0229] The indentation modulus is measured according to ISO 14577 (2002) from the slope in the load range of 65% to 95% of the maximum load in the unloading curve obtained when unloading the load-penetration curve of the indenter. The measurement conditions are as follows.

[0230] · Measurement device: Nanoindentation method dynamic ultra-micro hardness tester "trade name PICODENTOR HM500, (manufacturer FISCHER INSTRUMENTS KK)"

[0231] Indenter: Conical Berkovich-type diamond indenter with a face angle of 120°

[0232] ·Indenter penetration depth: 20μm

[0233] ·Indenter insertion speed: 12.5μm / sec

[0234] · Unloading speed of pressure head: 12.5m / s

[0235] The above measurement was performed on the surface (contact portion) of the cleaning blade that was in contact with the transfer counter-conveyor belt.

[0236] -Surface ratio of F and Si-

[0237] The ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade in contact with the transfer opposing conveyor belt to the total amount of F and Si present within 5 μm from the surface (surface ratio of F and Si) is 75% or more. By making the surface ratio of F and Si at the contact portion of the cleaning blade 75% or more, the friction of the contact portion of the cleaning blade is reduced, thereby suppressing the occurrence of wear. Furthermore, the surface ratio of F and Si at the contact portion of the cleaning blade is preferably 85% or more, and more preferably 90% or more, for example.

[0238] On the other hand, the upper limit of the surface ratio of F and Si at the contact portion of the cleaning blade is not particularly limited, but is preferably 95% or less, and more preferably 93% or less. When the surface ratio of F and Si at the contact portion of the cleaning blade is 95% or less, it is possible to suppress the occurrence of intermediate portion abutment (surface pressure drop) due to insufficient viscosity formation at the contact portion of the cleaning blade.

[0239] -Surface F and Si content-

[0240] The total amount of F and Si (surface F and Si amount) on the surface (contact portion) of the cleaning blade that contacts the transfer counter conveyor belt is, for example, preferably 15 atm% or more, more preferably 18 atm% or more, and further preferably 20 atm% or more. When the surface F and Si amount at the contact portion of the cleaning blade is 15 atm% or more, the friction of the contact portion of the cleaning blade is reduced, thereby suppressing the occurrence of wear.

[0241] The upper limits of the surface F and Si content at the contact portion of the cleaning blade are not particularly limited, but are preferably 25 atm % or less, more preferably 22 atm % or less, from the viewpoint of suppressing the occurrence of defects at the contact portion of the cleaning blade.

[0242] -50nm position F and Si amount-

[0243] The total amount of F and Si present at a position 50 nm from the surface (contact portion) of the cleaning blade that contacts the transfer opposing conveyor belt (the amount of F and Si at the 50 nm position) is, for example, preferably 0.3 atm% or more, more preferably 0.5 atm% or more, and further preferably 1.0 atm% or more. When the amount of F and Si at the 50 nm position of the cleaning blade is 0.3 atm% or more, the friction reduction at the contact portion of the cleaning blade can be sustained, thereby suppressing the occurrence of wear over time.

[0244] The upper limit of the F at the 50 nm position and the amount of Si in the cleaning blade is not particularly limited, but is preferably 7.0 atm % or less, more preferably 5.0 atm % or less, and even more preferably 2.0 atm % or less from the viewpoint of suppressing the occurrence of time-dependent defects at the contact portion of the cleaning blade.

[0245] The method for measuring the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade in contact with the transfer counter conveyor belt to the total amount of F and Si present within 5 μm from the surface (F and Si surface ratio) is described. That is, the method for analyzing the amount of F and Si in the depth direction from the contact portion of the cleaning blade is described.

[0246] The area including the surface (contact portion) of the cleaning blade in contact with the transfer counter conveyor belt was cut out, and the amounts (atm %) of each of N, C, O, F and Si elements were measured from the contact portion toward the depth direction using XPS (Versa Probe II manufactured by ULVAC-PHI, Inc.).

[0247] The total amount of F and Si present on the surface (contact portion) of the cleaning blade in contact with the transfer counter conveyor belt was obtained as follows: for the plot of the depth from the contact portion of the cleaning blade obtained by the analysis in the depth direction and the element ratio, the area to a depth of 5 μm was set as SA, and the area to a depth of 200 nm was set as SB, and the ratio was calculated according to the formula SB / SA×100. In addition, the total amount of F and Si present at a position 50 nm from the surface (contact portion) of the cleaning blade in contact with the transfer counter conveyor belt was also obtained in the same manner.

[0248] -structure-

[0249] The cleaning blade is made of polyurethane resin.

[0250] Polyurethane resin

[0251] The polyurethane resin is a polyurethane resin obtained by polymerizing at least a polyol component and a polyisocyanate component. The polyurethane resin may be a polyurethane resin obtained by polymerizing a resin having a functional group that can react with an isocyanate group of a polyisocyanate in addition to the polyol component as needed.

[0252] For example, the polyurethane resin preferably has a hard segment and a soft segment. The "hard segment" and the "soft segment" refer to segments in which the material constituting the former is composed of a relatively harder material than the material constituting the latter, and the material constituting the latter is composed of a relatively softer material than the material constituting the former.

[0253] In addition, as the material constituting the hard segment (hard segment material), there can be mentioned a low molecular weight polyol component among the polyol components, a resin having a functional group capable of reacting with an isocyanate group of a polyisocyanate, etc. On the other hand, as the material constituting the soft segment (soft segment material), there can be mentioned a high molecular weight polyol component among the polyol components.

[0254] Here, the average particle size of the aggregates of the hard segments is, for example, preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less.

[0255] By setting the average particle size of the hard segment aggregates to 1 μm or more, the frictional resistance on the contact member surface is easily reduced. Therefore, the blade behavior becomes stable and local wear is easily suppressed.

[0256] On the other hand, by setting the average particle size of the hard segment aggregates to 10 μm or less, the occurrence of chipping can be easily suppressed.

[0257] The average particle size of the hard segment aggregates was measured as follows: an image was captured at a magnification of ×20 using a polarizing microscope (BX51-P manufactured by Olympus Corporation), the image was processed to binarize the image, 5 points were measured on each cleaning blade (the particle size of 5 aggregates was measured at each point), the particle size (equivalent circle diameter) of the aggregates was measured for 20 cleaning blades, and the average particle size was calculated from a total of 500.

[0258] The image was binarized using image processing software OLYMPUS Stream essentials (manufactured by Olympus Corporation) to adjust the thresholds of hue / chroma / brightness so that the crystal part and the hard segment aggregates were black and the amorphous part (equivalent to the soft segment) was white.

[0259] Polyol ingredients

[0260] The polyol component includes high molecular weight polyols and low molecular weight polyols.

[0261] The high molecular weight polyol component is a polyol having a number average molecular weight of 500 or more (e.g., preferably 500 or more and 5000 or less). As the high molecular weight polyol component, polyester polyols obtained by dehydration condensation of low molecular weight polyols and dibasic acids, polycarbonate polyols obtained by reaction of low molecular weight polyols and alkyl carbonates, polycaprolactone polyols, polyether polyols and other well-known polyols can be cited. In addition, as commercially available products of high molecular weight polyols, for example, PLAXEL205 or PLAXEL240 manufactured by Daicel Corporation can be cited.

[0262] Here, the number average molecular weight is a value measured by gel permeation chromatography (GPC). The same shall apply hereinafter.

[0263] These high molecular weight polyols may be used alone or in combination of two or more.

[0264] The polymerization ratio of the high molecular weight polyol component can be, for example, 30 mol% to 50 mol%, preferably 40 mol% to 50 mol%, based on all the polymerization components of the polyurethane resin.

[0265] The low-molecular-weight polyol component is a polyol having a molecular weight (number average molecular weight) of less than 500. The low-molecular-weight polyol is a material that functions as a chain extender and a cross-linking agent.

[0266] Examples of the low molecular weight polyol component include 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosandiol. Among them, 1,4-butanediol is preferably used as the low molecular weight polyol component.

[0267] Examples of the low molecular weight polyol component include diol (bifunctional), triol (trifunctional) and tetraol (tetrafunctional) which are well known as chain extenders and crosslinking agents.

[0268] These polyols may be used alone or in combination of two or more.

[0269] The polymerization ratio of the low molecular weight polyol relative to all the polymerization components of the polyurethane resin can be, for example, greater than 50 mol% and less than 75 mol%, preferably greater than 52 mol% and less than 75 mol%, more preferably greater than 55 mol% and less than 75 mol%, and further preferably greater than 55 mol% and less than 60 mol%.

[0270] Polyisocyanate ingredients

[0271] Examples of the polyisocyanate component include 4,4-diphenylmethane diisocyanate (MDI), 2,6-toluene diisocyanate (TDI), 1,6-hexane diisocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), and 3,3′-dimethylbiphenyl-4,4′-diisocyanate (TODI).

[0272] As the polyisocyanate component, for example, 4,4′-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), and hexamethylene diisocyanate (HDI) are more preferable.

[0273] These polyisocyanate components may be used alone or in combination of two or more.

[0274] The polymerization ratio of the polyisocyanate component can be, for example, 5 mol% to 25 mol%, preferably 10 mol% to 20 mol%, based on all the polymerization components of the polyurethane resin.

[0275] Resins having functional groups capable of reacting with isocyanate groups

[0276] The resin having a functional group capable of reacting with an isocyanate group (hereinafter referred to as "functional group-containing resin") is preferably a flexible resin, and from the viewpoint of flexibility, an aliphatic resin having a linear structure is more preferred. Specific examples of the functional group-containing resin include acrylic resins containing two or more hydroxyl groups, polybutadiene resins containing two or more hydroxyl groups, and epoxy resins having two or more epoxy groups.

[0277] Examples of commercially available products of acrylic resins containing two or more hydroxyl groups include ACTFLOW manufactured by Soken Chemical & Engineering Co., Ltd. (grades: UMB-2005B, UMB-2005P, UMB-2005, UME-2005, etc.).

[0278] Examples of commercially available products of the polybutadiene resin containing two or more hydroxyl groups include R-45HT manufactured by IDEMITSU LUBE.

[0279] As the epoxy resin having two or more epoxy groups, for example, an epoxy resin having a hard and brittle property as conventional general epoxy resins is not preferred, and an epoxy resin having a softer and tougher property than conventional epoxy resins is preferred. As the above-mentioned epoxy resin, for example, from the viewpoint of molecular structure, an epoxy resin having a structure (flexible skeleton) capable of improving the mobility of the main chain in its main chain structure is preferred, and as the flexible skeleton, for example, an alkylene skeleton, a cycloalkane skeleton, a polyoxyalkylene skeleton, etc. can be cited, and a polyoxyalkylene skeleton is particularly preferred.

[0280] Furthermore, from the viewpoint of physical properties, epoxy resins having a lower viscosity than the molecular weight are preferred compared to existing epoxy resins. Specifically, for example, the weight average molecular weight is preferably within the range of 900±100, and the viscosity at 25°C is preferably within the range of 15000±5000 mPa·s, more preferably within the range of 15000±3000 mPa·s. Commercially available epoxy resins having such properties include, for example, EPICLON EXA-4850-150 manufactured by DIC CORPORATION.

[0281] The polymerization ratio of the functional group-containing resin is preferably set within a range that does not impair the characteristics of the cleaning blade, for example.

[0282] ·Production method of polyurethane resin

[0283] The polyurethane resin can be produced by a conventional polyurethane production method such as a prepolymer method or a one-shot method. The prepolymer method is suitable for this embodiment because it can produce polyurethane with excellent wear resistance and chipping resistance, but the method is not limited thereto.

[0284] The cleaning blade is produced by forming the cleaning blade-forming composition prepared by the above method into a sheet by centrifugal molding, extrusion molding, or the like, and then cutting the sheet.

[0285] Here, examples of the catalyst used in the production of the polyurethane resin include amine compounds such as tertiary amines, organic metal compounds such as quaternary ammonium salts and organic tin compounds, and the like.

[0286] Examples of the tertiary amine include trialkylamines such as triethylamine, tetraalkyldiamines such as N,N,N',N'-tetramethyl-1,3-butanediamine, amino alcohols such as dimethylethanolamine, ethoxylated amines, ethoxylated diamines, esteramines such as bis(diethylethanolamine) adipate, triethylenediamine (TEDA), cyclohexylamine derivatives such as N,N-dimethylcyclohexylamine, morpholine derivatives such as N-methylmorpholine and N-(2-hydroxypropyl)-dimethylmorpholine, piperazine derivatives such as N,N'-diethyl-2-methylpiperazine and N,N'-bis-(2-hydroxypropyl)-2-methylpiperazine, and the like.

[0287] Examples of the quaternary ammonium salt include 2-hydroxypropyltrimethylammonium-octylate, 1,5-diazabicyclo[4.3.0]nonene-5(DBN)-octylate, 1,8-diazabicyclo[5.4.0]undecene-7(DBU)-octylate, DBU-oleate, DBU-p-toluenesulfonate, DBU-formatate, and 2-hydroxypropyltrimethylammonium-formatate.

[0288] Examples of the organic tin compound include dialkyltin compounds such as dibutyltin dilaurate and dibutyltin di(2-ethylhexanoate), stannous 2-ethylhexanoate, and stannous oleate.

[0289] Among these catalysts, triethylenediamine (TEDA) which is a tertiary ammonium salt is used from the viewpoint of hydrolysis resistance, and a quaternary ammonium salt is used from the viewpoint of processability.

[0290] Among the quaternary ammonium salts, 1,5-diazabicyclo[4.3.0]nonene-5(DBN)-octanoate, 1,8-diazabicyclo[5.4.0]undecene-7(DBU)-octanoate, and DBU-formate, which have high reactivity, are used.

[0291] The content of the catalyst is, for example, preferably in the range of 0.0005% by mass or more and 0.03% by mass or less, and particularly preferably 0.001% by mass or more and 0.01% by mass or less, based on the entire polyurethane resin constituting the contact member.

[0292] These can be used alone or in combination of two or more.

[0293] ·Manufacturing of double-layer cleaning scraper

[0294] For example, when the cleaning blade has a two-layer structure of an edge layer and a back layer, the cleaning blade is produced by separately producing the edge layer and the back layer by the above-mentioned method for producing a polyurethane resin and bonding the obtained edge layer and back layer together.

[0295] When making the hardness of the edge layer and the back layer different from each other, a method of changing the material of the polyurethane resin can be mentioned, for example, a method of changing the ratio of the hard segment to the soft block can be mentioned.

[0296] Modification of contact parts

[0297] In this embodiment, since the ratio of the total amount of F and Si present within 200nm from the surface (contact portion) of the cleaning scraper in contact with the transfer opposing conveyor belt to the total amount of F and Si present within 5μm from the surface (surface ratio of F and Si) is set within the above-mentioned range, it is preferred to allow at least one of the F element and the Si element to penetrate into the contact portion of the obtained cleaning scraper, thereby having a modified layer that has been subjected to surface modification treatment.

[0298] The modified layer is a layer obtained by impregnating a surface treatment liquid containing an isocyanate compound, a specific polymer having at least one of F element and Si element, and an organic solvent into the contact portion of the cleaning blade and curing the surface treatment liquid (ie, the isocyanate compound and the specific polymer).

[0299] The modified layer is formed integrally with the surface layer of the contact portion so as to gradually become sparse from the surface toward the inside.

[0300] Examples of the isocyanate compound include 2,6-toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), p-phenylene diisocyanate (PPDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethylbiphenyl-4,4'-diisocyanate (TODI), and polymers thereof and modified products thereof. In addition, examples of modified products of the isocyanate compound include urethane prepolymers obtained by prepolymerizing an isocyanate compound with a polyol.

[0301] The specific polymer is preferably a compound that reacts with an isocyanate compound and chemically bonds thereto. Examples of acrylic polymers having a siloxane bond include block copolymers of (meth)acrylate and (meth)siloxane acrylate and derivatives thereof. In addition, "(meth)acrylic acid" means either or both of acrylic acid and methacrylic acid.

[0302] Examples of the acrylic polymer having a fluorine atom include a block copolymer of (meth)acrylic acid ester and fluoroalkyl methacrylate and a derivative thereof.

[0303] For example, the cleaning blade preferably contains a polymer having a siloxane bond (silicone-based polymer) at a portion in contact with the transfer-opposing conveyor belt.

[0304] Furthermore, from the viewpoint of solubility in an organic solvent, the specific polymer is preferably a compound having a hydroxyl group, an alkyl group, or a carboxyl group, for example.

[0305] In addition, as a method for confirming that the surface layer of the contact portion of the cleaning blade contains a specific polymer and a method for confirming that the surface layer contains a specific polymer that is an acrylic polymer, for example, the following method can be cited. Specifically, the confirmation is as follows: the structure estimation or composition analysis of the surface layer material of the contact portion of the cleaning blade is performed by an analysis method such as Fourier transform infrared spectrophotometer (FTIR) or X-ray photoelectron spectroscopy (XPS).

[0306] The content of the specific polymer in the surface treatment liquid is, for example, 8 parts by mass to 13 parts by mass, preferably 9 parts by mass to 13 parts by mass, and more preferably 10 parts by mass to 13 parts by mass, relative to 100 parts by mass of the isocyanate compound.

[0307] The organic solvent is preferably a solvent that dissolves the specific polymer and is compatible with the isocyanate compound, and specifically includes ethyl acetate, methyl ethyl ketone (MEK), toluene, acetone, cyclohexanone, etc. In addition, as the organic solvent, a reactive diluent such as 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, trimethylolpropane triacrylate, etc. can be used.

[0308] The modified layer is formed, for example, by impregnating and applying the surface treatment liquid to at least the contact portion of the cleaning blade, removing the organic solvent by drying, and forming a cured layer by heat treatment.

[0309] The impregnation coating method is not particularly limited, and examples thereof include common methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, curtain coating, etc. When the impregnation coating method is the impregnation coating method, the impregnation time may be, for example, in the range of 10 seconds to 60 seconds.

[0310] Drying conditions after impregnation coating include, for example, a temperature of 20° C. to 30° C. and a time of 1 minute to 10 minutes. Heat treatment conditions include, for example, a temperature of 50° C. to 80° C. and a time of 60 minutes to 90 minutes.

[0311] Pressing force

[0312] The pressing force NF (Normal Force) of the cleaning blade against the transfer opposing conveyor belt is preferably, for example, 1.5 gf / mm or more and 3.5 gf / mm or less, and more preferably 2.3 gf / mm or more and 3.2 gf / mm or less. When the pressing force NF is 1.5 gf / mm or more, it is possible to suppress the toner from leaking out at the contact position between the transfer opposing conveyor belt and the cleaning blade, and when the pressing force NF is 3.5 gf / mm or less, it is possible to suppress the toner from filming on the surface of the transfer opposing conveyor belt.

[0313] Here, the pressing force NF of the cleaning blade is calculated by the following formula.

[0314] Formula: Pressing force NF = k × d

[0315] Where k is the spring constant inherent to the cleaning blade, and d is the amount of penetration of the cleaning blade into the transfer belt (reference Figure 3 ).

[0316] The spring constant k inherent to the cleaning blade is obtained by displacing the cleaning blade 12 and measuring the load with a load cell.

[0317] Regarding the biting amount d of the cleaning blade with respect to the transfer counter conveyor belt, the cleaning blade 12 was fixed to a supporting member and the displacement amount of the cleaning blade when it was brought into contact with the transfer counter conveyor belt was calculated.

[0318] Here, in Figure 3 In the figure, BE denotes a transfer counter conveyor belt, CB denotes a cleaning blade, and CBS denotes a supporting member that supports the cleaning blade.

[0319] The amount of bite d of the cleaning blade into the transfer opposing conveyor belt is, for example, preferably not less than 0 mm and not more than 10 mm, and more preferably not less than 0.01 mm and not more than 5 mm.

[0320] (Transfer Opposite Conveyor Belt)

[0321] In this embodiment, a transfer counter-conveyor belt configured to contact the surface of the recording medium opposite to the surface on which the colorant image is transferred has, for example, a conductive elastic layer (substrate) containing a polymer material and conductive particles, and may also have a surface layer (protective layer) on at least one of the outer peripheral surface and the inner peripheral surface of the substrate.

[0322] Figure 1 This is a schematic perspective view showing an example of a transfer counter conveyor belt. Figure 1The transfer counter conveyor belt 50 shown in the figure has a base material (conductive elastic layer) 52, a protective layer (surface layer) 54, and a protective layer (surface layer) 56. The protective layer 54 is a layer provided on the outer peripheral surface of the base material 52 and constitutes the outer peripheral surface of the transfer counter conveyor belt 50. The protective layer 56 is a layer provided on the inner peripheral surface of the base material 52 and constitutes the inner peripheral surface of the transfer counter conveyor belt 50.

[0323] Hereinafter, the layer structure and materials of the transfer counter conveyor belt will be described in detail.

[0324] [Substrate (Conductive Elastic Layer)]

[0325] The substrate is preferably a film or sheet including conductive particles in a polymer material, for example.

[0326] Examples of the polymer material include rubber and resin. The polymer material may be used alone or in combination of two or more.

[0327] Examples of the rubber include chloroprene rubber, epichlorohydrin rubber, isoprene rubber, butyl rubber, polyurethane, silicone rubber, fluororubber, styrene-butadiene rubber, butadiene rubber, nitrile rubber (NBR), ethylene propylene rubber, ethylene-propylene-diene terpolymer rubber (EPDM), natural rubber, and mixed rubbers thereof.

[0328] Examples of the resin include polyamide, polyimide, polyamideimide, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyethersulfone, polyphenylsulfone, polysulfone, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polycarbonate, polyester, and mixed resins thereof.

[0329] As the conductive particles, for example, carbon black such as Ketjen black, oil furnace black, channel black, acetylene black, etc.; metal particles such as aluminum and nickel; metal oxide particles such as indium tin oxide, tin oxide, zinc oxide, titanium oxide, yttrium oxide, etc. are mentioned. As the conductive particles, for example, carbon black is preferred. The conductive particles may be used alone or in combination of two or more.

[0330] The average primary particle size of the conductive particles is, for example, preferably 1 nm or more and 150 nm or less, more preferably 3 nm or more and 100 nm or less, and further preferably 5 nm or more and 50 nm or less.

[0331] The substrate may contain a conductive agent other than the conductive particles. Examples of the conductive agent include ion conductive substances such as potassium titanate, potassium chloride, sodium perchlorate, and lithium perchlorate; and ion conductive polymers such as polyaniline, polyether, polypyrrole, polysulfone, and polyacetylene. The conductive agent may be used alone or in combination of two or more.

[0332] The substrate is preferably, for example, a conductive elastic layer containing rubber and conductive particles, and more preferably a conductive elastic layer containing at least one of chloroprene rubber and epichlorohydrin rubber and carbon black.

[0333] The total content of the conductive particles and the conductive agent contained in the substrate is preferably set based on the volume resistivity of the transfer opposing conveyor belt, for example. The volume resistivity of the transfer opposing conveyor belt is preferably 1.0×10 6 Ω·cm or more and 1.0×10 9 Ω·cm or less.

[0334] In the present embodiment, the volume resistivity (Ω·cm) is measured as follows.

[0335] The measurement environment is a temperature of 22°C and a relative humidity of 55%. The sample is placed in the measurement environment for more than 24 hours to adjust the temperature and humidity. The resistance measuring instrument is a microammeter (R8430A manufactured by Advantest Company), and the probe is a UR probe (manufactured by Mitsubishi Chemical Corporation). The applied voltage is 1 kV, the application time is 5 seconds, and the load is 1 kgf. The measurement points are 6 points at equal intervals on the circumference of the transfer opposing conveyor belt, and 3 points in the central part and both ends of the transfer opposing conveyor belt in the width direction, a total of 18 points. The measured values ​​of the 18 points are arithmetic averaged.

[0336] When the substrate contains carbon black, the content of the carbon black is, for example, preferably 5 parts by mass or more and 40 parts by mass or less relative to 100 parts by mass of the polymer material.

[0337] The substrate may contain additives such as antioxidants, crosslinking agents, flame retardants, colorants, surfactants, dispersants, fillers, etc.

[0338] From the viewpoint of durability of the transfer opposing conveyor belt, the average thickness of the substrate is, for example, preferably 400 μm or more, more preferably 420 μm or more, and further preferably 440 μm or more. From the viewpoint of flexibility and bending resistance of the transfer opposing conveyor belt, the average thickness of the substrate is, for example, preferably 800 μm or less, more preferably 600 μm or less, and further preferably 500 μm or less.

[0339] [Protective layer (surface layer)]

[0340] The transfer opposing conveyor belt may include a protective layer on at least one of the outer circumference and the inner circumference of the substrate, for example, preferably includes a protective layer on the outer circumference and the inner circumference of the substrate. The protective layer provided on the outer circumference of the substrate constitutes the outer circumference of the transfer opposing conveyor belt. The protective layer provided on the inner circumference of the substrate constitutes the inner circumference of the transfer opposing conveyor belt.

[0341] The protective layer is preferably a film or sheet containing a polymer material, for example.

[0342] Examples of the polymer material include the rubbers and resins described above for the base material.

[0343] The protective layer preferably contains, for example, a urethane resin and fluorine-containing resin particles.

[0344] Urethane resin (also called polyurethane or urethane rubber) is generally synthesized by polymerizing polyisocyanate and polyol. For example, the urethane resin preferably has a hard segment and a soft segment.

[0345] As the fluorine-containing resin particles, for example, one or more particles of tetrafluoroethylene resin (polytetrafluoroethylene), trifluorochloroethylene resin, hexafluoropropylene resin, vinyl fluoride resin, vinylidene fluoride resin, difluorodichloroethylene resin and copolymers thereof are preferably included. Among them, as the fluorine-containing resin particles, for example, tetrafluoroethylene resin (polytetrafluoroethylene resin) particles are preferred.

[0346] The content of the fluorine-containing resin particles in the protective layer is preferably 35% by mass or more, and more preferably 38% by mass or more, from the viewpoint of reducing the friction of the contact portion with the cleaning blade and thus suppressing the wear of the cleaning blade. On the other hand, the upper limit of the content of the fluorine-containing resin particles in the protective layer is preferably 50% by mass or less, and more preferably 45% by mass or less, from the viewpoint of the smoothness of the surface layer.

[0347] The protective layer preferably contains 35% by mass or more of tetrafluoroethylene resin (polytetrafluoroethylene) particles, for example, and the upper limit of the content is preferably 50% by mass or less.

[0348] The average primary particle size of the fluorine-containing resin particles is, for example, preferably from 5 nm to 300 nm, more preferably from 8 nm to 200 nm, further preferably from 10 nm to 150 nm.

[0349] The protective layer may contain additives such as antioxidants, crosslinking agents, flame retardants, colorants, fillers, etc.

[0350] Regarding the average thickness of the protective layer, on a single side of the substrate, from the viewpoint of the wear resistance of the protective layer, it is, for example, preferably greater than 2 μm, more preferably greater than 5 μm, and further preferably greater than 10 μm, and from the viewpoint of the flexibility and bending resistance of the transfer opposing conveyor belt, it is, for example, preferably less than 60 μm, more preferably less than 30 μm, and further preferably less than 20 μm.

[0351] [Manufacturing method of transfer opposing conveyor belt]

[0352] As a method for producing the transfer opposing conveyor belt, for example, there can be mentioned a method of preparing a tubular member as a base material and forming a protective layer on the outer peripheral surface or the inner peripheral surface of the tubular member.

[0353] The manufacturing method of the tubular component includes, for example, extrusion molding in which a composition containing a polymer material and conductive particles is melted, extruded from a mold in a strip shape and solidified; injection molding in which a composition containing a polymer material and conductive particles is melted, placed in a strip-shaped mold and solidified; coating molding in which a composition containing a precursor or monomer of a polymer material and conductive particles is coated on a core and solidified, etc.

[0354] The protective layer can be formed by, for example, applying a liquid composition containing a polymer material and fluorine-containing resin particles to the outer circumference or inner circumference of the tubular member and curing it; applying a liquid composition containing a precursor or monomer of a polymer material and fluorine-containing resin particles to the outer circumference or inner circumference of the tubular member and curing it, etc. In order to cure the liquid composition, drying, heating, electron beam irradiation or ultraviolet irradiation can be performed depending on the types of components.

[0355] (Structure of Image Forming Apparatus)

[0356] The image forming device involved in this embodiment comprises: an image holder; a charging member for charging the surface of the image holder; an electrostatic latent image forming member for forming an electrostatic latent image on the surface of the charged image holder; a developing member for accommodating an electrostatic latent image developer containing a colorant having colorant particles, and developing the electrostatic latent image formed on the surface of the image holder into a colorant image by the electrostatic latent image developer; a transfer member for transferring the colorant image formed on the surface of the image holder to the surface of a recording medium, and having a transfer opposing conveyor belt in contact with the side (back side) of the recording medium opposite to the side on which the colorant image is transferred; and a cleaning device having a cleaning scraper, wherein the cleaning scraper is in contact with the outer peripheral surface of the transfer opposing conveyor belt and cleans it.

[0357] Well-known image forming devices such as a device having a transfer member for transferring a colorant image on an image holder to a recording medium via a secondary transfer member (for example, a secondary transfer belt); a device having a fixing member for fixing the colorant image transferred to the surface of the recording medium; a device having a cleaning device for cleaning the surface of the image holder before charging after transferring the colorant image; a device having a static elimination device for eliminating static electricity by irradiating the surface of the image holder with static elimination light after transferring the colorant image and before charging; a device having an image holder heating member for increasing the temperature of the image holder and lowering the relative temperature, etc. are applicable to the image forming device involved in this embodiment.

[0358] The image forming apparatus according to the present embodiment may be any of a dry developing system image forming apparatus and a wet developing system (development system using a liquid developer) image forming apparatus.

[0359] In the image forming apparatus according to the present embodiment, for example, the portion including the image holder may be a cartridge structure (process cartridge) that is detachable from the image forming apparatus. As the process cartridge, for example, a process cartridge including a toner image forming device and a transfer device is preferably used.

[0360] (Image Forming Method)

[0361] The image forming method involved in this embodiment includes: a charging process, which charges the surface of the image retaining body; an electrostatic latent image forming process, which forms an electrostatic latent image on the surface of the charged image retaining body; a developing process, which develops the electrostatic latent image formed on the surface of the image retaining body into a colorant image by using an electrostatic latent image developer containing a colorant having colorant particles; a transfer process, which brings a transfer opposing conveyor belt into contact with the surface of the recording medium on the opposite side to the surface on which the colorant image is transferred, so as to transfer the colorant image formed on the surface of the image retaining body to the surface of the recording medium; and a cleaning process, which brings a cleaning scraper into contact with the outer peripheral surface of the transfer opposing conveyor belt and cleans it.

[0362] In the toner particles, the releasing agent present in a region within 800 nm from the surface accounts for 70% or more of the releasing agent in the entire toner particles, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less.

[0363] The cleaning blade is made of polyurethane resin. The indentation elastic modulus of the surface of the cleaning blade in contact with the transfer counter conveyor belt is 15 MPa or more and 35 MPa or less. Furthermore, the total amount of F and Si present within 200 nm from the surface of the cleaning blade in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.

[0364] Hereinafter, an example of the image forming apparatus and the image forming method according to the present embodiment will be described with reference to the accompanying drawings. However, the image forming apparatus and the image forming method according to the present embodiment are not limited thereto. In addition, the main parts shown in the drawings will be described, and the description of other parts will be omitted.

[0365] Figure 2 It is a schematic configuration diagram showing an example of the image forming apparatus according to the present embodiment.

[0366] Figure 2The image forming apparatus shown in the figure includes first to fourth image forming units 10Y, 10M, 10C, 10K (image forming members) of an electrophotographic method for printing images of yellow (Y), magenta (M), cyan (C), and black (K) colors based on color-separated image data. These image forming units (hereinafter, sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachable from the image forming apparatus.

[0367] An intermediate transfer belt (an example of an intermediate transfer body) 20 is provided above each unit 10Y, 10M, 10C, and 10K so as to extend through each unit. The intermediate transfer belt 20 is provided so as to be wound around a driving roller 22 and a supporting roller 24 that are in contact with the inner surface of the intermediate transfer belt 20, and to travel in a direction from the first unit 10Y toward the fourth unit 10K.

[0368] The backup roller 24 is urged away from the driving roller 22 by a spring (not shown) and applies tension to the intermediate transfer belt 20 wound around the intermediate transfer belt 20. An intermediate transfer belt cleaning device 30 is provided on the image holding surface side of the intermediate transfer belt 20 so as to face the driving roller 22.

[0369] The yellow, magenta, cyan and black toners contained in the toner cartridges 8Y, 8M, 8C and 8K are respectively supplied to the developing devices (an example of developing members) 4Y, 4M, 4C and 4K of the units 10Y, 10M, 10C and 10K.

[0370] The first to fourth units 10Y, 10M, 10C, and 10K have the same structure and operation, and therefore the first unit 10Y disposed on the upstream side in the traveling direction of the intermediate transfer belt and forming a yellow image will be described as a representative.

[0371] The first unit 10Y has a photoreceptor 1Y. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging member) 2Y, which charges the surface of the photoreceptor 1Y with a predetermined potential; an exposure device (an example of an electrostatic latent image forming member) 3, which forms an electrostatic latent image by exposing the charged surface using a laser beam 3Y based on a color-separated image signal; a developing device (an example of a developing member) 4Y, which supplies charged toner to the electrostatic latent image to develop the electrostatic latent image; a primary transfer roller (an example of a primary transfer member) 5Y, which transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device 6Y, which removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.

[0372] The primary transfer roller 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoreceptor 1Y. A bias power source (not shown) for applying a primary transfer bias is connected to each of the primary transfer rollers 5Y, 5M, 5C, and 5K of each unit.

[0373] The conveyor belt unit 60 is a conveyor belt unit including the transfer counter conveyor belt 50. The conveyor belt unit 60 includes the transfer counter conveyor belt 50, a driving roller 62, and a support roller 64.

[0374] The conveyor belt unit 60 is disposed outside the intermediate transfer belt 20 and is provided at a position facing the support roller 24. The conveyor belt unit 60 is connected to a bias power source (not shown) for applying a secondary transfer bias.

[0375] A transfer opposing conveyor belt cleaning blade 66 is detachably provided on the transfer opposing conveyor belt 50 of the conveyor belt unit 60 . The transfer opposing conveyor belt cleaning blade 66 removes residual toner or paper powder on the transfer opposing conveyor belt 50 after secondary transfer and cleans the outer peripheral surface of the transfer opposing conveyor belt 50 .

[0376] Next, the operation of forming a yellow image in the first unit 10Y will be described.

[0377] First, before the operation is performed, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.

[0378] The photoreceptor 1Y has a conductivity (for example, a volume resistivity of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ω·cm or less. Usually, the photosensitive layer has a high resistance (resistance of a general resin), but has a property that the resistivity of the portion irradiated with the laser beam changes when irradiated with a laser beam. Therefore, the laser beam 3Y is irradiated from the exposure device 3 to the surface of the charged photoreceptor 1Y according to the yellow image data sent from the control unit (not shown). As a result, an electrostatic latent image of the yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0379] An electrostatic latent image refers to an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image. It is formed as follows: a laser beam 3Y is used to reduce the resistivity of the irradiated portion of the photosensitive layer, thereby allowing the charged charge on the surface of the photoreceptor 1Y to flow, while on the other hand, the charge on the portion not irradiated by the laser beam 3Y remains.

[0380] The electrostatic latent image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y travels. Then, at the development position, the electrostatic latent image on the photoreceptor 1Y is developed by the developing device 4Y and visualized as a toner image.

[0381] The developing device 4Y contains, for example, an electrostatic latent image developer containing at least a yellow toner and a carrier. The yellow toner is frictionally charged by being stirred inside the developing device 4Y, and is held on a developer roller (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoreceptor 1Y. Then, by passing the surface of the photoreceptor 1Y through the developing device 4Y, the yellow toner is electrostatically attached to the latent image portion on the surface of the photoreceptor 1Y from which static electricity has been removed, thereby developing the latent image with the yellow toner. The photoreceptor 1Y on which the yellow toner image is formed continues to travel at a preset speed, so that the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.

[0382] When the yellow toner image on the photoreceptor 1Y is conveyed to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time has a (+) polarity opposite to the polarity (-) of the toner, and is controlled by a control unit (not shown) to, for example, +10 μA in the first unit 10Y.

[0383] The primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled based on the first unit.

[0384] In this manner, the intermediate transfer belt 20 after the yellow toner image is transferred by the first unit 10Y is transported sequentially through the second to fourth units 10M, 10C, and 10K, and transfers are performed multiple times so that the toner images of the respective colors are superimposed.

[0385] The intermediate transfer belt 20 to which the four-color toner image has been transferred multiple times after passing through the first to fourth units arrives at the secondary transfer section composed of the intermediate transfer belt 20, the support roller 24, and the conveyor belt unit 60. On the other hand, at a preset timing, the recording paper (an example of a recording medium) P is supplied to the gap between the conveyor belt unit 60 and the intermediate transfer belt 20 via the supply mechanism, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has the same polarity (-) as the polarity (-) of the toner, and the electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. The secondary transfer bias at this time is determined based on the resistance detected by the resistance detection member (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0386] The recording paper P to which the toner image is transferred is conveyed to the pressure contact portion (nip portion) of a pair of fixing rollers of a fixing device (an example of a fixing member) 28, and the toner image is fixed to the recording paper P to form a fixed image. The recording paper P after the color image is fixed is conveyed to the discharge portion, thereby completing a series of color image forming operations.

[0387] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, etc. Examples of the recording medium include, in addition to the recording paper P, OHP films, etc.

[0388] On the other hand, after the transfer onto the recording paper P is completed, the residual colorant remaining on the transfer opposing conveyor belt 50 is transported to the transfer opposing conveyor belt cleaning scraper 66 as the transfer opposing conveyor belt 50 rotates, and is removed from the transfer opposing conveyor belt 50 by the transfer opposing conveyor belt cleaning scraper 66.

[0389] As mentioned above, although this embodiment was demonstrated, it is not interpreted as being limited to the said embodiment, Various deformation|transformation, change, and improvement are possible.

[0390] Example

[0391] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0392] [Example 1]

[0393] <Preparation of electrostatic latent image developer>

[0394] -Preparation of amorphous polyester resin dispersion-

[0395] (Preparation of polyester resin dispersion (APE1))

[0396] Terephthalic acid: 30 mol parts

[0397] Fumaric acid: 70 mol parts

[0398] Bisphenol A ethylene oxide adduct: 5 mol parts

[0399] Bisphenol A propylene oxide adduct: 95 mol parts

[0400] The above materials were placed in a 5-liter flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor, and a distillation tower, and the temperature was raised to 210°C over 1 hour. 1 part of tetraethoxytitanium was added to 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 230°C over 0.5 hours, and the dehydration condensation reaction was continued at this temperature for 1 hour, and then the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized.

[0401] After adding 40 parts of ethyl acetate and 25 parts of 2-butanol to a container equipped with a temperature regulating member and a nitrogen replacement member to prepare a mixed solvent, 100 parts of a polyester resin was gradually added to dissolve it, and a 10% by mass ammonia aqueous solution (equivalent to 3 times the acid value of the resin in terms of molar ratio) was added and stirred for 30 minutes.

[0402] Next, the interior of the container was replaced with dry nitrogen, and the temperature was maintained at 40°C. While stirring the mixed solution, 400 parts of deionized water was added dropwise at a rate of 2 parts / min to emulsify the mixture. After the addition was completed, the emulsion was returned to room temperature (20°C to 25°C), and while stirring, dry nitrogen was bubbled for 48 hours to reduce ethyl acetate and 2-butanol to less than 1,000 ppm, thereby obtaining a resin particle dispersion in which resin particles with a volume average particle size of 200 nm were dispersed. Deionized water was added to the resin particle dispersion to adjust the solid content to 20% by mass, which was used as a polyester resin particle dispersion (APE1).

[0403] -Preparation of Colorant Particle Dispersion-

[0404] (Preparation of Colorant Particle Dispersion Liquid (Black Pigment Dispersion Liquid))

[0405] Carbon black (Regal 330 manufactured by Cabot Corporation): 250 parts

[0406] Anionic surfactant (NEOGEN SC manufactured by DKS Co. Ltd.): 33 parts (active ingredient: 60%. 8% relative to the colorant)

[0407] Deionized water: 750 parts

[0408] 280 parts of deionized water and 33 parts of anionic surfactants were placed in a stainless steel container whose height of the liquid level became about 1 / 3 of the height of the container when all the above components were put into the container. After the surfactant was fully dissolved, all the solid solution pigments were put into the container, and a stirrer was used to stir until there was no pigment that was not wetted, and defoaming was fully carried out. After defoaming, the remaining deionized water was added, and after a homogenizer (IKA company system, ULTRA TURRAX T50) was used to disperse for 10 minutes at 5000 revolutions, agitator was used to stir for 1 day and night, and defoaming was carried out. After defoaming, a homogenizer was used again to disperse for 10 minutes at 6000 revolutions, and agitator was used to stir for 1 day and night, and defoaming was carried out. Then, a high-pressure impact dispersion machine ULTIMAIZER (SUGINOMACHINE LIMITED system, HJP30006) was used to disperse the dispersion liquid with a pressure of 240MPa. According to the total loading amount and the processing capacity of the device, about 25 dispersions were carried out. The obtained dispersion was left for 72 hours, the precipitate was removed, and deionized water was added to adjust the solid content concentration to 15% to obtain a colorant particle dispersion. The volume average particle size D50 of the particles in the colorant particle dispersion was 135 nm.

[0409] (Preparation of Release Agent Dispersion)

[0410] (Preparation of Release Agent Dispersion (WAX1))

[0411] Paraffin wax (HNP9 manufactured by NIPPON SEIRO CO., LTD., melting temperature 75°C): 270 parts

[0412] Anionic surfactant (NEOGEN RK manufactured by DKS Co. Ltd., active ingredient amount: 60%): 13.5 parts (3.0% based on the release agent in terms of active ingredient)

[0413] Deionized water: 21.6 parts

[0414] The above components were mixed, and the release agent was dissolved in a pressure-dispensing homogenizer (manufactured by Gaulin Co., Ltd., Gaulin Homogenizer) at an internal liquid temperature of 120°C, and then dispersed at a dispersion pressure of 5 MPa for 120 minutes, and then dispersed at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion (WAX1). The volume average particle size D50 of the particles in the release agent dispersion (WAX1) was 225 nm. Then, deionized water was added to adjust the solid content concentration to 20.0%.

[0415] -Preparation of mixed particle dispersion-

[0416] (Preparation of mixed particle dispersion (RW1))

[0417] After mixing 150 parts of a polyester resin particle dispersion (APE1), 20 parts of a release agent particle dispersion (WAX1) and 2.9 parts of an anionic surfactant (Dowfax2A1 manufactured by The Dow Chemical Company), 1.0% nitric acid was added at 25°C to adjust the pH to 3.0, thereby obtaining a mixed particle dispersion (RW1).

[0418] -Preparation of toner-

[0419] Polyester resin particle dispersion (APE1): 700 parts

[0420] Colorant particle dispersion: 133 parts

[0421] Deionized water: 400 parts

[0422] Anionic surfactant (manufactured by The Dow Chemical Company, Dowfax 2A1): 2.9 parts

[0423] The above components were placed in a 3-liter reaction container equipped with a thermometer, a pH meter, and a stirrer, and 1.0% nitric acid was added at a temperature of 25°C to adjust the pH to 3.0. Then, 130 parts of the prepared aluminum sulfate aqueous solution were added while dispersing at 5,000 rpm using a homogenizer (IKA Japan: ULTRA TURRAX T50) and dispersion was carried out for 6 minutes.

[0424] Then, a stirrer and a hood heater were set in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was fully stirred, while the temperature was raised to 40°C at a heating rate of 0.2°C / min, and the temperature was raised at a heating rate of 0.05°C / min from above 40°C. Every 10 minutes, the particle size was measured using Multisizer II (aperture: 50μm, Beckman Coulter, Inc.). When the volume average particle size reached 5.0μm, the temperature was maintained, and 450 parts of the mixed particle dispersion (RW1) were added for 5 minutes. After keeping it for 30 minutes, the pH was adjusted to 9.0 using a 1% sodium hydroxide aqueous solution. Then, every 5°C, the pH was adjusted to 9.0 in the same way, while the temperature was raised to 85°C at a heating rate of 1°C / min, and it was maintained. The particle shape and surface properties were observed using an optical microscope and a scanning electron microscope (FE-SEM). As a result, aggregation of particles was confirmed at 5.0 hours, so the container was cooled to 30° C. using cooling water over 5 minutes.

[0425] The cooled slurry was passed through a nylon mesh with a pore size of 15 μm to remove coarse powder, and the toner slurry after passing through the mesh was filtered under reduced pressure using an aspirator. The toner remaining on the filter paper was crushed into fine particles by hand, and deionized water 10 times the amount of the toner was added at a temperature of 30°C, and stirred and mixed for 30 minutes. Next, the toner was filtered under reduced pressure using an aspirator, and the toner remaining on the filter paper was crushed into fine particles by hand, and deionized water 10 times the amount of the toner was added at a temperature of 30°C. After stirring and mixing for 30 minutes, the toner was filtered under reduced pressure again using an aspirator, and the conductivity of the filtrate was measured. This operation was repeated until the conductivity of the filtrate became less than 10 μS / cm, and the toner was washed. After the washed toner was crushed into fine particles using a wet dry granulator (COMIL), it was vacuum dried in an oven at 35°C for 36 hours to obtain toner particles.

[0426] Then, 3.3 parts of silica particles were added as an external additive to 100 parts of the toner particles, and then mixed for 3 minutes at a peripheral speed of 30 m / s using a Henschel mixer. Then, the mixture was sieved using a vibration sieve with an aperture of 45 μm to obtain a toner.

[0427] -Carrier production-

[0428] 500 parts of spherical magnetite particle powder with a volume average particle size of 0.18 μm were added to a Henschel mixer and stirred thoroughly. Then, 5 parts of a titanate coupling agent were added, the temperature was raised to 95° C., and the mixture was stirred for 30 minutes to obtain spherical magnetite particles coated with a titanate coupling agent.

[0429] Next, 6 parts of phenol, 10 parts of 30% formalin, 500 parts of magnetite particles, 7 parts of 25% ammonia water and 400 parts of water were placed in a 1L four-necked flask and mixed and stirred. Then, while stirring, the temperature was raised to 90°C within 60 minutes, and the reaction was carried out at the same temperature for 180 minutes, then cooled to 30°C, 500 ml of water was added, the supernatant was removed, and the precipitate was washed with water. It was dried at 180°C under reduced pressure, and the coarse powder was removed using a sieve with a mesh of 106 μm to obtain core particles with an average particle size of 38 μm.

[0430] Next, 200 parts of toluene and 35 parts of a styrene-methyl methacrylate copolymer (component molar ratio of 10:90, weight average molecular weight of 160,000) were stirred in a stirrer for 90 minutes to obtain a coating resin solution.

[0431] 1000 parts of the core particles and 70 parts of the coating resin solution were placed in a vacuum degassing type kneading coater (the gap between the rotor and the wall surface was 35 mm), maintained at 65°C, stirred at 30 rpm for 30 minutes, and then the temperature was brought to 88°C, the pressure was reduced, toluene was distilled off, degassed and dried. Then, it was passed through a sieve with a mesh size of 75 μm. The shape factor SF2 of the carrier was 104.

[0432] -Production of developer-

[0433] 8 parts of toner and 100 parts of carrier were mixed with a V mixer to prepare a developer.

[0434] -Toner Properties-

[0435] The ratio of the releasing agent present in the region within 800 nm from the surface of the toner particles to the releasing agent in the entire toner particles (surface ratio of the releasing agent) was measured by the above method. The melting temperature of the releasing agent was also measured by the above method.

[0436] <Cleaning Blade Production>

[0437] At 115°C, 100 parts by mass of polycaprolactone polyol (molecular weight 2000) as a high molecular weight polyol component and 58 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI: manufactured by DIC Corporation) as a polyisocyanate component were reacted for 20 minutes. Then, 6.1 parts by mass of 1,4-butanediol and 2.6 parts by mass of trimethylolpropane as low molecular weight polyol components were mixed and heated and cured for 40 minutes in a mold maintained at 140°C. After molding, a rubber elastic body cut into a width of 14 mm, a thickness of 1.9 mm, and a length of 330 mm was prepared, and the rubber elastic body was bonded to a support plate to prepare a scraper base material.

[0438] 80 parts by mass of ethyl acetate as an organic solvent, 25 parts by mass of 4,4′-diphenylmethane diisocyanate (MDI: “Millionate MT” manufactured by TOSOH CORPORATION, melting point: 38° C.) as an isocyanate compound, and 5 parts by mass of a silicone-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.) as an acrylic polymer having a siloxane bond (specific polymer) were dispersed and mixed in a ball mill for 5 hours to obtain a surface treatment liquid.

[0439] The scraper substrate was immersed in the surface treatment liquid for 60 seconds while the surface treatment liquid was kept at 23°C, and then dried for 1 minute at room temperature (25°C). Then, the surface of the dried scraper substrate was wiped clean with a sponge containing a small amount of toluene, and then dried for 1 minute at 25°C, and heated in an oven kept at 25°C for 50 minutes to obtain a cleaning scraper.

[0440] -Physical properties of cleaning blade-

[0441] The above method was used to measure the ratio of the total amount of F and Si within 200nm of the surface in contact with the transfer opposing conveyor belt to the total amount of F and Si within 5μm from the surface (surface ratio of F, Si), the total amount of F and Si on the surface in contact with the transfer opposing conveyor belt (surface F, Si amount (atm%)), and the total amount of F and Si at a position 50nm away from the surface in contact with the transfer opposing conveyor belt (50nm position F, Si amount (atm%)).

[0442] <Production of transfer counter conveyor belt>

[0443] Fabrication of conductive elastic layer

[0444] A conductive rubber material containing carbon black and ethylene propylene diene rubber were mixed in chloroprene rubber, extruded by a mixing extruder, and dried with hot air to obtain a tubular body with a diameter (outer diameter) of 40 mm and an average thickness of 450 μm. The tubular body was cut into a length of 355 mm as a substrate (conductive elastic layer).

[0445] ·Surface layer production

[0446] A coating liquid was prepared by adding 1% by mass of a curing agent (LOCTITE WH-1, Henkel Japan Ltd.) to a urethane resin containing PTFE (polytetrafluoroethylene) particles (BONDERITE T862A, Henkel Japan Ltd., PTFE content of 65% by mass), followed by dilution with water.

[0447] The coating liquid was spread on the outer peripheral surface of the substrate while the substrate was rotated so that the central axis of the substrate was in the horizontal direction. Then, hot air drying was performed at a temperature of 150°C for 35 minutes, thereby forming a surface layer with an average thickness of 10 μm on the outer peripheral surface of the substrate. Then, the same coating liquid was spread on the inner peripheral surface of the substrate, and hot air drying was performed in the same manner, thereby forming a surface layer with an average thickness of 10 μm on the inner peripheral surface of the substrate.

[0448] In this manner, a transfer opposing conveyor belt having surface layers on both surfaces of the substrate (conductive elastic layer) was obtained.

[0449] <Image forming device>

[0450] The object obtained by the above was installed in an image forming apparatus "FUJIFILM Business Innovation Corp., Versant 3100i Press" as an electrostatic latent image developer, a transfer opposing conveyor belt (a conveyor belt in contact with the surface of the recording medium opposite to the surface to which the toner image is transferred) and a cleaning blade for the transfer opposing conveyor belt. In addition, regarding the installation conditions of the cleaning blade for the transfer opposing conveyor belt, the pressing force NF (Normal Force, gf / mm) was set to the conditions described in Table 1, and the angle W / A (Working Angle) was set to 10°.

[0451] [Examples 2 to 12, Comparative Examples 1 to 5]

[0452] <Preparation of electrostatic latent image developer>

[0453] In Example 1, a release agent is selected for the preparation of a release agent dispersion, and the amount of a mixed particle dispersion (RW1) is adjusted when preparing a colorant, thereby preparing colorant particles that satisfy the "surface ratio of the release agent (%)" and "melting temperature of the release agent (°C)" recorded in Tables 1 and 2 to obtain an electrostatic latent image developer.

[0454] In addition, as the release agent having the melting temperature shown in Table 1 and Table 2, the following release agents were used, and these waxes were prepared alone or in an arbitrary ratio to adjust to a desired melting temperature.

[0455] · Paraffin wax (manufactured by NIPPON SEIRO CO., LTD., melting temperature 64°C)

[0456] · Paraffin wax (HNP9 manufactured by NIPPON SEIRO CO., LTD., melting temperature 75°C)

[0457] ·Ester wax (manufactured by NOF CORPORATION, melting temperature 82°C)

[0458] Fischer-Tropsch wax (manufactured by NIPPON SEIRO CO., LTD., FNP-0090, melting temperature 90°C)

[0459] <Cleaning Blade Production>

[0460] In Example 1, the amount of 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by TOSOH CORPORATION, melting point: 38°C) used in forming a cleaning scraper is adjusted, and the composition of the surface treatment liquid used in the surface modification treatment of the contact portion of the obtained scraper substrate and the conditions of the surface heat treatment are changed to produce a cleaning scraper that meets the "surface ratio of F and Si (%)", "surface F and Si amount (atm%)", "50nm position F and Si amount (atm%)", and "100% modulus (MPa)" recorded in Table 2.

[0461] In addition, when the "silicone-based polymer" in Table 1 and Table 2 was used as the surface treatment liquid, a treatment liquid was used in which ethyl acetate, 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by TOSOH CORPORATION, melting point: 38°C) as an isocyanate compound, and a silicone-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.) as an acrylic polymer having a siloxane bond were mixed. On the other hand, when the "fluorine compound" in Table 1 and Table 2 was used, a treatment liquid mixed with a fluorine-silicone-modified acrylic polymer (8FS-009; manufactured by Taisei Fine Chemical Co., Ltd.) was used instead of the silicone-modified acrylic polymer (8BS-9000).

[0462] <Production of transfer counter conveyor belt>

[0463] In Example 1, the conductive particles used when preparing the substrate (conductive elastic layer) were changed as described in Tables 1 and 2 to obtain a transfer opposing conveyor belt.

[0464] Carbon black (Mitsubishi Chemical Corporation, #3230B)

[0465] Tin oxide (Showa Kako Corp., stannous oxide)

[0466] Zinc oxide (Made by TAYCA Co., Ltd., MZ-300)

[0467] <Evaluation test>

[0468] (1) Missed scraping

[0469] Using the image forming apparatus prepared in each example and comparative example, 10,000 images were printed in an environment of temperature 10° C. and humidity 20% RH, and then a blank image (ie, an image with an image density of 0%) was printed and evaluated according to the following criteria.

[0470] G0: No streaks

[0471] G1: Three or fewer slight streaks that can be detected through a microscope (but not with the naked eye)

[0472] G2: More than 3 slight streaks that can be detected by microscope (not visible to the naked eye)

[0473] G3: Less than 3 slight streaks visible to the naked eye

[0474] G4: More than 3 slight lines visible to the naked eye

[0475] G5: Produces clear line fringes

[0476] (2) Film formation

[0477] Using the image forming apparatus prepared in each embodiment and comparative example, 1000 images were printed in an environment of temperature 28°C and humidity 80% RH. Then, the observed image of the transfer opposing conveyor belt surface was binarized in a 100 μm square, and the area ratio occupied by the attached matter was calculated and evaluated according to the following criteria.

[0478] G0: No attachment (the attachment ratio is 0%)

[0479] G1: Slight adhesion (the adhesion ratio is less than 1%)

[0480] G2: The attachment ratio is 1% or more and less than 3%

[0481] G3: The attachment ratio is 3% or more and less than 5%

[0482] G4: The attachment ratio is 5% or more and less than 10%

[0483] G5: The attachment ratio is more than 10%

[0484] (3) Wear

[0485] Using the image forming apparatus prepared in each example and comparative example, 10,000 images were printed in an environment of temperature 28° C. and humidity 80% RH, and then the wear depth of the cleaning blade was measured and evaluated according to the following criteria.

[0486] G0: No wear

[0487] G1: Slight wear (wear depth greater than 0 μm and less than 0.2 μm)

[0488] G2: Wear depth is 0.2 μm or more and less than 0.4 μm

[0489] G3: Wear depth is 0.4 μm or more and less than 1.0 μm

[0490] G4: Wear depth is 1.0 μm or more and less than 2.0 μm

[0491] G5: Wear depth is 2.0μm or more

[0492] (4) Defects

[0493] In order to conduct the defect evaluation test, a transfer counter conveyor belt having a protrusion of 5 μm in height and 20 μm in width on the outer peripheral surface was prepared. The transfer counter conveyor belt was installed in the image forming apparatus prepared in each embodiment and comparative example, and after printing 100 images under an environment of temperature 10°C and humidity 20% RH, the defect depth of the cleaning blade corresponding to the position of the protrusion was measured and evaluated according to the following criteria.

[0494] G0: No defect

[0495] G1: Slight defect (defect depth is more than 0μm and less than 1μm)

[0496] G2: Defect depth is 1 μm or more and less than 2 μm

[0497] G3: Defect depth is 2 μm or more and less than 4 μm

[0498] G4: Defect depth is 4 μm or more and less than 6 μm

[0499] G5: Defect depth is 6μm or more

[0500]

[0501]

[0502] As shown in Table 1 and Table 2, it can be seen that the image forming apparatus of this embodiment can suppress toner filming on the transfer opposing conveyor belt surface and suppress abrasion of the cleaning blade compared to the comparative example.

[0503] This embodiment includes the following aspects.

[0504] (((1)))An image forming apparatus comprising:

[0505] Image holding body;

[0506] a charging member for charging the surface of the image holding member;

[0507] an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member;

[0508] A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent of the entire toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer;

[0509] a transfer member having a transfer counter-conveyor belt in contact with a surface of a recording medium opposite to a surface on which the toner image is transferred, and transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; and

[0510] A cleaning device having a cleaning scraper, the cleaning scraper contacts with and cleans the outer peripheral surface of the transfer counter conveyor belt, and is made of a polyurethane resin, the indentation elastic modulus at the surface in contact with the transfer counter conveyor belt is greater than 15 MPa and less than 35 MPa, and the total amount of F and Si existing within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si existing within 5 μm from the surface.

[0511] (((2)))The image forming apparatus according to (((1))), wherein:

[0512] The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.

[0513] (((3)))The image forming apparatus according to (((1))) or (((2))), wherein:

[0514] The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.

[0515] (((4)))The image forming apparatus according to any one of (((1))) to (((3))), wherein:

[0516] The indentation elastic modulus of the cleaning blade is 20 MPa or more and 30 MPa or less.

[0517] (((5)))The image forming apparatus according to any one of (((1))) to (((4))), wherein:

[0518] In the cleaning blade, the total amount of F and Si present within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.

[0519] (((6)))The image forming apparatus according to any one of (((1))) to (((5))), wherein:

[0520] In the cleaning blade, a total amount of F and Si present on a surface in contact with the transfer opposing conveyor belt is 15 atm % or more.

[0521] (((7)))An image forming device according to (((6))), wherein:

[0522] In the cleaning blade, a total amount of F and Si present on a surface in contact with the transfer opposing conveyor belt is 18 atm % or more and 25 atm % or less.

[0523] (((8)))The image forming apparatus according to any one of (((1))) to (((7))), wherein:

[0524] In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface in contact with the transfer opposing conveyor belt is 0.3 atm % or more.

[0525] (((9)))An image forming device according to (((8))), wherein:

[0526] In the cleaning blade, a total amount of F and Si present at a position 50 nm from a surface in contact with the transfer opposing conveyor belt is 0.3 atm % or more and 2.0 atm % or less.

[0527] (((10)))The image forming apparatus according to any one of (((1))) to (((9))), wherein:

[0528] The cleaning blade contains a silicone polymer in a surface layer that contacts the transfer opposing conveyor belt.

[0529] (((11)))The image forming apparatus according to any one of (((1))) to (((10))), wherein:

[0530] The cleaning blade contacts the transfer counter conveyor belt with a pressing force of 1.5 gf / mm or more and 3.5 gf / mm or less.

[0531] (((12)))The image forming apparatus according to any one of (((1))) to (((11))), wherein:

[0532] The transfer counter conveyor belt includes a conductive elastic layer containing carbon black and a surface layer containing 35 mass % or more of polytetrafluoroethylene particles.

[0533] (((13)))An image forming method comprising:

[0534] A charging process to charge the surface of the image holding body;

[0535] An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member;

[0536] A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less;

[0537] a transfer step of bringing a transfer counter conveyor belt into contact with a surface of a recording medium opposite to a surface on which the toner image is transferred, so as to transfer the toner image formed on the surface of the image holder to the surface of the recording medium; and

[0538] A cleaning process, wherein a cleaning scraper is brought into contact with the outer peripheral surface of the transfer counter conveyor belt and cleans it, wherein the cleaning scraper is made of polyurethane resin, and the indentation elastic modulus at the surface in contact with the transfer counter conveyor belt is greater than 15 MPa and less than 35 MPa, and the total amount of F and Si within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si within 5 μm from the surface.

[0539] According to the invention involved in (((1))), there is provided an image forming apparatus in which colorant filming on the surface of a transfer opposing conveyor belt is suppressed and wear of a cleaning scraper is suppressed, compared to an image forming apparatus having a cleaning scraper having an indentation elastic modulus exceeding 35 MPa at the surface in contact with a transfer opposing conveyor belt or a cleaning scraper having a total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing conveyor belt that is less than 75% of the total amount of F and Si present within 5 μm from the surface.

[0540] According to the invention of (((2))), an image forming apparatus having excellent low-temperature fixing property of an image is provided, compared to an image forming apparatus in which the amount of releasing agent present in a region within 800 nm from the surface of the toner particle is less than 75% of the releasing agent in the entire toner particle.

[0541] According to the invention involved in (((3))), there is provided an image forming device having excellent low-temperature fixing property of an image compared to an image forming device in which the melting temperature of a release agent exceeds 75°C, and there is provided an image forming device in which the formation of a toner film on the surface of a transfer opposing conveyor belt is suppressed compared to an image forming device in which the melting temperature of a release agent is lower than 70°C.

[0542] According to the invention involved in (((4))), there is provided an image forming device having an indentation elastic modulus of less than 20 MPa compared to the cleaning scraper, thereby suppressing the leakage of colorant at the contact position between the transfer opposing conveyor belt and the cleaning scraper, and there is provided an image forming device having an indentation elastic modulus of more than 30 MPa compared to the cleaning scraper, thereby suppressing the formation of colorant film on the surface of the transfer opposing conveyor belt.

[0543] According to the invention involved in (((5))), there is provided an image forming apparatus in which the wear at the contact portion of the cleaning scraper is suppressed compared to an image forming apparatus having a cleaning scraper in which the total amount of F and Si existing within 200nm from the surface in contact with the transfer opposing conveyor belt is less than 85% of the total amount of F and Si existing within 5μm from the surface.

[0544] According to the invention of (((6))) or (((7))), there is provided an image forming apparatus in which wear at the contact portion of the cleaning scraper is suppressed compared to an image forming apparatus having a cleaning scraper having a total amount of F and Si less than 15 atm% on a surface in contact with a transfer opposing conveyor belt.

[0545] According to the invention of (((8))) or (((9))), there is provided an image forming apparatus in which the wear over time at the contact portion of the cleaning scraper is suppressed compared to an image forming apparatus having a cleaning scraper in which the total amount of F and Si present at a position 50 nm from the surface in contact with the transfer opposing conveyor belt is less than 0.3 atm%.

[0546] According to the invention of (((10))), there is provided an image forming apparatus in which wear of the contact portion of the cleaning blade is suppressed compared to an image forming apparatus having a cleaning blade whose surface layer in contact with a transfer opposing conveyor belt does not contain a silicone polymer but contains a fluorine compound.

[0547] According to the invention involved in (((11))), there is provided an image forming device in which a cleaning scraper contacts a transfer counter conveyor belt with a pressing force less than 1.5 gf / mm, thereby suppressing the occurrence of colorant leakage at the contact position between the transfer counter conveyor belt and the cleaning scraper; and there is provided an image forming device in which a cleaning scraper contacts a transfer counter conveyor belt with a pressing force greater than 3.5 gf / mm, thereby further suppressing the occurrence of colorant filming on the surface of the transfer counter conveyor belt.

[0548] According to the invention of (((12))), there is provided an image forming apparatus in which the transfer counter conveyor belt has a conductive elastic layer that does not contain carbon black, thereby suppressing the occurrence of toner leakage at the contact position between the transfer counter conveyor belt and the cleaning blade.

[0549] According to the invention involved in (((13))), there is provided an image forming method in which colorant filming on the surface of a transfer opposing conveyor belt is suppressed and wear of the cleaning scraper is suppressed, compared to a cleaning process including using a cleaning scraper having an indentation elastic modulus exceeding 35 MPa at the surface in contact with the transfer opposing conveyor belt or a cleaning scraper in which the total amount of F and Si present within 200 nm from the surface in contact with the transfer opposing conveyor belt is less than 75% of the total amount of F and Si present within 5 μm from the surface.

[0550] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the art can understand the present invention through various variations optimized for specific uses assumed to be various embodiments. The scope of the present invention is defined by the above claims and their equivalents.

[0551] Explanation of symbols

[0552] 1Y, 1M, 1C, 1K-photoreceptor, 2Y, 2M, 2C, 2K-charging roller (an example of a charging member), 3-exposure device (an example of an electrostatic latent image forming member), 3Y, 3M, 3C, 3K-laser beam, 4Y, 4M, 4C, 4K-developing device (an example of a developing member), 5Y, 5M, 5C, 5K-primary transfer roller (an example of a primary transfer member), 6Y, 6M, 6C, 6K-photoreceptor cleaning device, 8Y, 8M, 8C, 8K-toner cartridge, 1 0Y, 10M, 10C, 10K-image forming unit, 20-intermediate transfer belt (an example of an intermediate transfer body), 22-driving roller, 24-supporting roller, 28-fixing device (an example of a fixing component), 30-intermediate transfer belt cleaning device, 50-transfer counter conveyor belt, 52-base material layer, 54-protective layer, 56-protective layer, 60-conveyor belt unit, 62-driving roller, 64-supporting roller, 66-transfer counter conveyor belt cleaning scraper, P-recording paper (an example of a recording medium).

Claims

1. An image forming device comprising: Image holding body; a charging member for charging the surface of the image holding member; an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member; A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent of the entire toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer; a transfer member having a transfer counter conveyor belt in contact with a surface of the recording medium opposite to the surface on which the toner image is transferred, and transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; and A cleaning device having a cleaning scraper, the cleaning scraper contacts with and cleans the outer peripheral surface of the transfer counter conveyor belt, and is made of a polyurethane resin, the indentation elastic modulus at the surface in contact with the transfer counter conveyor belt is greater than 15 MPa and less than 35 MPa, and the total amount of F and Si existing within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si existing within 5 μm from the surface.

2. The image forming apparatus according to claim 1, wherein: The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.

3. The image forming apparatus according to claim 1 or 2, wherein: The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.

4. The image forming apparatus according to any one of claims 1 to 3, wherein: The indentation elastic modulus of the cleaning blade is 20 MPa or more and 30 MPa or less.

5. The image forming apparatus according to any one of claims 1 to 4, wherein: In the cleaning blade, the total amount of F and Si present within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.

6. The image forming apparatus according to any one of claims 1 to 5, wherein: In the cleaning blade, a total amount of F and Si present on a surface in contact with the transfer opposing conveyor belt is 15 atm % or more.

7. The image forming apparatus according to claim 6, wherein: In the cleaning blade, a total amount of F and Si present on a surface in contact with the transfer opposing conveyor belt is 18 atm % or more and 25 atm % or less.

8. The image forming apparatus according to any one of claims 1 to 7, wherein: In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface in contact with the transfer opposing conveyor belt is 0.3 atm % or more.

9. The image forming apparatus according to claim 8, wherein: In the cleaning blade, a total amount of F and Si present at a position 50 nm from a surface in contact with the transfer opposing conveyor belt is 0.3 atm % or more and 2.0 atm % or less.

10. The image forming apparatus according to any one of claims 1 to 9, wherein: The cleaning blade contains a silicone polymer in a surface layer that contacts the transfer opposing conveyor belt.

11. The image forming apparatus according to any one of claims 1 to 10, wherein: The cleaning blade contacts the transfer counter conveyor belt with a pressing force of 1.5 gf / mm or more and 3.5 gf / mm or less.

12. The image forming apparatus according to any one of claims 1 to 11, wherein: The transfer counter conveyor belt includes a conductive elastic layer containing carbon black and a surface layer containing 35 mass % or more of polytetrafluoroethylene particles.

13. An image forming method, comprising: A charging process to charge the surface of the image holding body; An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member; A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of bringing a transfer counter conveyor belt into contact with a surface of a recording medium opposite to a surface on which the toner image is transferred, so as to transfer the toner image formed on the surface of the image holder to the surface of the recording medium; and A cleaning process, wherein a cleaning scraper is brought into contact with the outer peripheral surface of the transfer counter conveyor belt and cleans it, wherein the cleaning scraper is made of polyurethane resin, and the indentation elastic modulus at the surface in contact with the transfer counter conveyor belt is greater than 15 MPa and less than 35 MPa, and the total amount of F and Si within 200 nm from the surface in contact with the transfer counter conveyor belt accounts for more than 75% of the total amount of F and Si within 5 μm from the surface.

Citation Information

Patent Citations

  • Cleaning blade

    JP2001051565A